Carbon nanotube dispersion, cathode paste and cathode
Patent Information
- Application Number
- JP2024540551
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-29
- Filing Date
- 2022-05-20
- Publication Date
- 2025-04-04
AI Technical Summary
Existing dispersions of single- and double-walled carbon nanotubes for lithium-ion battery cathodes face challenges with high viscosity during storage and application, leading to instability and non-uniform mixing, which affects the quality and stability of the cathode material.
A dispersion method using hydrogenated nitrile butadiene rubber (HNBR) and single- or double-walled carbon nanotubes, adjusted to have a specific viscosity range that remains stable during storage and lowers viscosity during processing, ensuring high stability and processability.
The method produces a cathode slurry with high viscosity during storage and low viscosity during application, maintaining dispersion stability and ensuring uniform coating on the current collector, resulting in high-quality lithium-ion battery cathodes with improved cycle stability and capacity.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to liquid dispersions of single-walled and / or double-walled carbon nanotubes and aggregates thereof, which dispersions have both high stability and moderate viscosity. The present invention also relates to a method for producing such dispersions. The present invention also relates to the use of such dispersions for producing cathode slurries. The present invention also relates to cathode slurries and methods for producing lithium ion battery cathodes. [Background technology]
[0002] Dispersions of single-walled and double-walled carbon nanotubes can be used to introduce these carbon nanomaterials into various coatings and composites, including cathode slurries for the production of lithium-ion battery cathodes. The presence of single-walled and double-walled carbon nanotubes in the cathode of a lithium-ion battery can improve its technical properties: reducing the internal resistance and increasing the specific capacity and the number of charging cycles (i.e., increasing the battery capacity after a certain number of charging and discharging cycles). However, the single-walled and / or double-walled carbon nanotubes should be optimally dispersed and distributed in the lithium-ion battery cathode material to achieve this technical result.
[0003] Single-walled and double-walled carbon nanotubes tend to bundle and aggregate into more complicated shapes. Although the aggregation of carbon nanotubes into long and thick bundles is desirable in some embodiments, including for example to ensure high electrical conductivity of the cathode, it leads to a faster settling rate of the dispersed carbon nanotube aggregates, i.e., a lower stability of the dispersion or cathode slurry. A lower stability of the dispersion leads to a shorter storage time of the dispersion, which limits possible logistics and technical schemes, and increases the risk of non-uniform subsequent mixing with the cathode slurry material, which in turn increases the risk of rejects in lithium-ion battery manufacturing. These risks are related to a greater extent to the lower stability of the cathode slurry containing single-walled and / or double-walled carbon nanotubes and their aggregates.
[0004] Methods for improving the stability of dispersions by preventing the aggregation of dispersed particles such as carbon nanotubes using dispersants and surfactants are known in the art. In the case of single-walled carbon nanotubes, for example, chlorosulfonic acid is known to completely shift the equilibrium of the aggregation process towards individual nanotubes [ANG Parra-Vasquez, N. Behabtu, MJ Green, CL Pint, CC Young, J. Schmidt, E. Kesselman, A. Goyal, PM Ajayan, Y. Cohen, Y. Talmon, RH Hauge, M. Pasquali, Spontaneous Dissolution of Ultralong Single-and Multiwalled Carbon Nanotubes, ACS Nano 2010 4(7), pp.3969-3978]. However, this approach has the drawback that the long bundles of carbon nanotubes are reduced or eliminated in the dispersion, although their presence is advantageous in some embodiments since it reduces the electrical percolation threshold and increases the electrical conductivity of coatings or composites (e.g., lithium ion battery cathodes) obtained using this type of dispersion.
[0005] On the other hand, dispersions of single- or double-walled carbon nanotubes are characterized by a high viscosity, which grows with the increase in the concentration of nanotubes and their bundles and their length-to-thickness ratio [ANG Parra-Vasquez, JG Duque, MJ Green, M. Pasquali, Assessment of length and bundle distribution of dilute single-walled carbon nanotubes by viscosity measurements, AIChE J., 60 (2014), pp. 1499-1508]. Further aggregation of carbon nanotube bundles into complex shaped aggregates leads to very high viscosity of the dispersion, making further utilization of the dispersion technically difficult, for example for coating or pumping through process lines in manufacturing processes.
[0006] At the same time, high viscosity of the dispersion reduces the mobility of the carbon nanotubes and their bundles and the settling rate of the aggregates, thus improving the stability of the dispersion. Conversely, the mobility and settling rate of the aggregates are higher in low viscosity dispersions. Thus, the selection of a carbon nanotube dispersion involves finding the middle ground between the high stability of the dispersion and its low viscosity.
[0007] Thus, including the process of producing cathode slurries for lithium-ion batteries, there is a technical challenge of obtaining a dispersion in which high stability of the dispersion and the opportunity for long-term storage without peeling and property changes are combined with the low viscosity required for the use of the dispersion. A similar technical challenge exists for cathode slurries containing single-walled and / or double-walled carbon nanotubes, which must ensure its high viscosity during storage before use (application to the cathode current collector), and high viscosity after application to the current collector without spreading to ensure good quality of the edges of the cathode active material layer, and at the same time ensure low viscosity of the cathode slurry under the processing conditions defined for application to the current collector.
[0008] There are solutions for the production of highly viscous gels containing carbon nanotubes in a dispersed state. WO 2006112162 proposes a gel containing dispersed carbon nanotubes based on ionic liquids, such as those obtained by neutralization reaction of benzoic acid or its derivatives and a base. This gel containing carbon nanotubes offers the possibility of unlimited long-term storage without aggregation of the nanotubes and settling of these aggregates. However, the use of ionic liquids as dispersions greatly limits the applications of the dispersion. For most applications, including the production of cathode slurries, this gel cannot be used directly, but a dispersion based on aqueous and / or organic solvents containing mainly electrically neutral molecules must be obtained therefrom before use. The stability of this dispersion is no longer guaranteed by the stability of the initial gel, nor that of the cathode slurry. Furthermore, in many embodiments, including the production of cathode slurries and lithium ion battery cathodes, the initial component of the ionic liquid may be undesirable even after dilution and dispersion in a solvent.
[0009] Solutions are known in which the composition of the dispersion is selected so that the viscosity of the dispersion and / or its complex modulus is in a narrow range, intermediate between the high viscosity necessary to keep the good quality of the carbon nanotube dispersion and the low viscosity desired for good workability of transporting and converting this dispersion into the final product. For example, EP 3333946 claims a dispersion of carbon nanotube bundles in a dispersion medium, which also contains 1-15% by weight of hydrogenated nitrile butadiene rubber obtained by hydrogenation of conjugated dienes, the dispersion further characterized by a complex modulus of 20-500 Pa at 1 Hz. The inventors of EP 3333946 use the complex modulus at 1 Hz as a measure of the fluid viscosity: at a low complex modulus the fluid viscosity is too low; at a high complex modulus the liquid viscosity is too high if the further manufacturing process (formation of the electrode) is not technically feasible. As described in the cited patent, the viscosity of the dispersions with the above complex modulus is between 2 and 20 Pa·s at a shear rate of 1 / (6.3 s). EP 3333946 does not aim to ensure high stability of the dispersion. However, limiting the viscosity below 20 Pa·s is not sufficient for the dispersion to remain stable for long periods, which is a drawback that prevents an efficient organization of the production process, including good storage and transport of the dispersion. EP 3333946 has been selected as the prototype.
[0010] technical challenges There is therefore a technical problem of obtaining a dispersion of single-walled and / or double-walled carbon nanotubes, characterized both by high stability during storage and transport and by a low viscosity of this dispersion under the various technological processes of its use, including the manufacture of a cathode slurry of a lithium-ion battery and then of a cathode. There is a similar technical problem with cathode slurries containing single-walled and / or double-walled carbon nanotubes, which requires obtaining a cathode slurry characterized by a high viscosity during storage before use (application to the current collector of the cathode), a high viscosity after application to the current collector without spreading to ensure good quality at the edge of the active material layer of the cathode, and at the same time a low viscosity of the cathode slurry under the conditions of the technological process of application to the current collector. As a result, there is a problem of producing high-quality lithium-ion battery cathodes, which are manifested in a high specific capacity and stability of operation in successive charge-discharge cycles. Known solutions, including those in EP 3333946, do not make it possible to solve the technical problem. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] International Publication No. 2006112162 [Patent Document 2] European Patent No. 3333946 [Non-patent literature]
[0012] [Non-Patent Document 1] ANGParra-Vasquez, N. Behabtu, MJ Green, CLPint, CC Young, J. Schmidt, E. Kesselman, A. Goyal, PMAjayan, Y. Cohen, Y. Talmon, RH Hauge, M. Pasquali, Spontaneous Dissolution of Ultralong Single-and Multiwalled Carbon Nanotubes, ACS Nano 2010 4(7), pp. 3969-3978 [Non-Patent Document 2] ANGParra-Vasquez, JGDuque, MJGreen, M.Pasquali,Assessment of length and bundle distribution of dilute single-walled carbon nanotubes by viscosity measurements,AIChE J.,60(2014),pp.1499-1508 Summary of the Invention
[0013] To solve the technical problem, the dispersion at rest during storage must be a highly viscous fluid, i.e. the dispersion viscosity is 1 / 6.3 s, which allows for long-term storage and / or transportation of the dispersion without aggregation and / or settling of the carbon nanotubes. -1 at shear rates below 20 Pa·s, and at the same time the dispersion viscosity in the process stream must be significantly lower, 18.6 s -1 The viscosity must be less than 2 Pa·s at shear rates above 1 / 6.3 s, i.e. sufficiently low for the technological processes in which the dispersion is applied, including the technological process of preparing the cathode slurry. Hereinafter, the term "viscosity" refers to the kinematic viscosity at a temperature of 25°C. The storage and application conditions of the dispersion may be characterized by different temperatures. Importantly, the typical shear rates during storage and transportation given here and used below (<1 / 6.3 s) are also important. -1 ) and shear rate during processing (>18.6s -1 ) is not absolute and is considered a convention for the quantitative description of dispersion viscosity. The shear rate is 1 / 6.3s for some transport conditions. -1 In some technological processes using dispersions, the -1 This does not negate the advantages of the dispersion of the present invention.
[0014] Research carried out by the inventors of the present application has shown that it is possible to produce dispersions of single- and double-walled carbon nanotubes and their aggregates which are non-ideal pseudoplastic fluids and which obey the Ostwald-de Waele power law known for some non-ideal liquids [W. Ostwald, "Ueber die rechnerische Darstellung des Strukturgebietes der Viscositat", Colloid-Zeitschrift 47 (1929), pp. 176-187]. JPEG2024545798000002.jpg2069
[0015] This law dictates that their viscosity depends on the shear rate in liquid flow, i.e. the lower the viscosity, the higher the shear rate. Pseudoplastic fluids are characterized by n<1. The lower the flow behavior index n, the more pronounced the dependence of pseudoplastic fluid viscosity on shear rate. Further studies have shown that the flow behavior index can be significantly reduced by adding a gelling agent in a dispersion of single-walled and / or double-walled carbon nanotubes, which can be used to achieve particularly significant effects in organic solvents when using hydrogenated butadiene-nitrile rubber (HNBR, hydrogenated acrylonitrile butadiene rubber) as a gelling agent. The simultaneous introduction of HNBR and single-walled and / or double-walled carbon nanotubes gives a synergistic effect that results in a lower flow behavior index n (i.e. a greater difference between the dispersion and an ideal Newtonian fluid) compared to the flow behavior index of the corresponding dispersion of a solution or suspension of carbon nanotubes in a solvent and HNBR in a solvent.
[0016] The synergistic effect results from the formation of HNBR gel domains in the suspension that are interconnected by bundles of single-walled and / or double-walled carbon nanotubes. The resulting network provides very high dispersion viscosity at low shear loads. However, the intermolecular bonds between the carbon nanotubes and the HNBR molecules are weak enough that higher shear loads will break them, resulting in lower viscosity.
[0017] The present disclosure provides a dispersion containing a solvent in which most of the molecules are electrically neutral, hydrogenated nitrile butadiene rubber, and single-walled and / or double-walled carbon nanotubes, the content of the single-walled and / or double-walled carbon nanotubes being in the range of 0.2 to 2 wt %, and the weight ratio of the single-walled and / or double-walled carbon nanotubes to the hydrogenated nitrile butadiene rubber being at least 0.1 and not more than 10.
[0018] Dispersions with this composition can be prepared at low shear rates (e.g., 1 / 6.3 s) due to the synergistic effect on viscosity of single-walled and / or double-walled carbon nanotubes and HNBR. -1 The very high dynamic viscosity of the dispersion at shear rates typical for processing (e.g., 18.6 s -1 It has the advantage of low kinematic viscosity at ultra low temperatures.
[0019] Hydrogenated nitrile butadiene rubber (HNBR) refers to a polymer obtained by hydrogenation of nitrile butadiene rubber, i.e., a polymer obtained by copolymerization of acetonitrile and butadiene. HNBR contains -CH2-CH(CN)-acetonitrile units, polybutadiene units and hydrogenated polybutadiene units. The term "polybutadiene units" refers to -СH2-CH=CH-CH2- (1,4-polybutadiene units) or >СH-CH=CH2 (1,2-polybutadiene units) polymer chain units, and the term "hydrogenated polybutadiene units" refers to -СH2-CH2-CH2-CH2- or >CH-CH2-CH3 polymer chain units, respectively, i.e., saturated units obtained by hydrogenation of polybutadiene units. In some embodiments, for example, Therban® 3406 or Therban® 3404 are preferably used as fully hydrogenated rubbers containing less than 1% by weight of residual polybutadiene units. In some embodiments, it is preferred to use partially hydrogenated rubbers, such as Therban® 3496, having a residual content of polybutadiene units of greater than 3% by weight, or greater than 5% by weight, or greater than 17% by weight.
[0020] The preferred content of hydrogenated polybutadiene units in the HNBR is greater than 15% by weight. The most preferred content of hydrogenated polybutadiene units in the HNBR is greater than 40% by weight.
[0021] In some cases, the HNBR preferably contains more than 20% by weight of acetonitrile units. In some cases, the hydrogenated nitrile butadiene rubber ML (1+4) The viscosity at 100° C. is preferably less than 50 Mooney units. In some embodiments, such low viscosity nitrile-butadiene rubbers are preferably fully hydrogenated, i.e., contain less than 1% by weight of residual polybutadiene units, such as Therban® 3404.
[0022] The presence of HNBR in the dispersion results in a higher flow consistency index K and a lower flow behavior index n. The presence of single-walled and / or double-walled carbon nanotubes and / or their agglomerates in the dispersion also results in an increase in the flow consistency index K and a decrease in the flow behavior index n. The simultaneous presence of HNBR and single-walled and / or double-walled carbon nanotubes and / or their agglomerates in the dispersion results in a synergistic effect, which is expressed in a lower flow behavior index n (i.e. a larger difference between the dispersion and an ideal Newtonian fluid) compared to the flow behavior index of the corresponding dispersion of carbon nanotubes in a solvent and HNBR in a solvent.
[0023] The content of single-walled and / or double-walled carbon nanotubes in the dispersion that allows the technical result to be achieved is 0.2-2 wt.%. The preferred content of single-walled and / or double-walled carbon nanotubes in the dispersion is determined by the technical equipment used and the logistic characteristics. Preferably, the content of single-walled and / or double-walled carbon nanotubes is 0.3-1.4 wt.%. In some embodiments, the content of single-walled and / or double-walled carbon nanotubes is preferably 0.3-0.6 wt.%, most preferably 0.35-0.45 wt.%. In some other embodiments, the content of single-walled and / or double-walled carbon nanotubes in the dispersion is preferably 0.6-1.2 wt.%, most preferably 0.7-1 wt.%.
[0024] The preferred weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the dispersion is at least 0.2 and not more than 5. The most preferred weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the dispersion is at least 0.5 and not more than 3. However, synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the dispersion ranging from 0.1 to 0.5. In some embodiments, the most preferred weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the dispersion is at least 0.5 and not more than 5. Synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the dispersion ranging from 3 to 10.
[0025] The presence of single-walled and / or double-walled carbon nanotubes in the dispersion is an important condition for achieving technical results. Single-walled carbon nanotubes are known to have small diameters, less than 4 nm, for example 1.5 nm, for stable single-walled carbon nanotubes, and at the same time large lengths that can exceed 5 μm. Single-walled carbon nanotubes therefore have a very large length-to-diameter ratio that can exceed 3000. Double-walled carbon nanotubes are also known to have an outer diameter that does not exceed 6 nm (for example, can be 2.8 nm), and their length can also exceed 5 μm. The aggregation of single-walled and / or double-walled carbon nanotubes can form aggregates with a length-to-diameter ratio that is somewhat smaller or larger than the length-to-diameter ratio of the individual nanotubes contained therein. Preferably, the single-walled and / or double-walled carbon nanotube aggregates contain bundles of single-walled and / or double-walled carbon nanotubes having a length-to-diameter ratio of greater than 100, more preferably a length-to-diameter ratio of single-walled and / or double-walled carbon nanotubes of greater than 500, and most preferably a length-to-diameter ratio of single-walled and / or double-walled carbon nanotubes of greater than 1000.
[0026] The ability of single-walled and / or double-walled carbon nanotubes to interact and aggregate (bundle) with each other via van der Waals forces (π-π interactions) is also very important to achieve technical results. Defects in single-walled and / or double-walled carbon nanotubes reduce this ability. Therefore, single-walled and / or double-walled carbon nanotubes preferably contain as few defects as possible. A quantitative indicator of the number of defects in the structure of single-walled and / or double-walled carbon nanotubes is the ratio of the G-band and D-band intensities in the Raman spectrum; the higher this ratio, the less defective the carbon nanotubes are. The preferred peak intensity ratio of the G-band and D-band in the Raman spectrum at 532 nm is at least 10, the more preferred intensity ratio of the G-band and D-band in the Raman spectrum at 532 nm is at least 40, even more preferred the G-band and D-band intensity ratio in the Raman spectrum at 532 nm is at least 60, and the most preferred ratio is at least 80.
[0027] In many embodiments involving the preparation of the cathode slurry and further cathode preparation, the single-walled and / or double-walled carbon nanotubes in the dispersion are preferably aggregated, with the mode of the number hydrodynamic diameter distribution of the carbon nanotube aggregates being in the range of 100 nm to 1 μm. Most preferably, the mode of the number hydrodynamic diameter distribution of the carbon nanotube aggregates is in the range of 300 nm to 800 nm. In this case, the number hydrodynamic diameter distribution of the carbon nanotube aggregates can be characterized by more than one mode, e.g., bimodal or trimodal. The number size distribution of suspended particles (such as bundles of carbon nanotubes) is commonly determined by dynamic light scattering (DLS), which allows the effective hydrodynamic diameter D via the well-known Stokes-Einstein relationship. h The suspended particle diffusion coefficient D, which is related to diff can be determined.
[0028] As mentioned above, the ability of single-walled and / or double-walled carbon nanotubes to interact and aggregate (bundle) with each other via van der Waals forces (π-π interactions) is also important to achieve technical results, but this is particularly important to ensure the stability of the cathode slurry, which requires dispersion for its manufacture. The length of a significant portion of the bundles preferably exceeds the typical size of the cathode active material, for example more than 10 μm. It should therefore be noted that the length of the bundles of single-walled and / or double-walled carbon nanotubes significantly exceeds the hydrodynamic diameter. The Stokes-Einstein relationship for cylindrical particles (nanotubes and their bundles) with length L and diameter d, averaged over all possible orientations, is given by equation (2): JPEG2024545798000003.jpg1796
[0029] See N. Nair, W. Kim, RD Braatz, MS Strano, Dynamics of Surfactant-Suspended Single-Walled Carbon Nanotubes in a Centrifugal Field, Langmuir, 2008, Vol. 24, pp. 1790-1795 doi:10.1021 / la702516u, or by equation (3) if the particles are assumed to be prolate spheroids. JPEG2024545798000004.jpg27152
[0030] See J. Gigault, I. Le Hecho, S. Dubascoux, M. Potin-Gautier, G. Lespes, Single-walled carbon nanotube length determination by asymmetrical-flow field-flow fractionation hyphenated to multi-angle laser-light scattering, J. Chromatogr. A, 2010, Vol. 1217, pp. 7891-7897.
[0031] The two models (2) and (3) yield very similar values of the shape factor, which indicates how many times larger the bundle length is than its effective hydrodynamic diameter. Considering that the length-to-diameter ratio of most nanotube bundles in suspension is in the range between 100 and 10,000, the shape factor is in the narrow range of 5 to 10. Thus, the length L of the carbon nanotube bundle can be estimated by up to two times from the value of the effective hydrodynamic diameter in equation (4).
[0032] JPEG2024545798000005.jpg1169
[0033] It is therefore preferred that the hydrodynamic diameter distribution of single-walled and / or double-walled carbon nanotube aggregates (bundles) is characterized by more than one mode and / or at least one mode is greater than 2 μm.
[0034] The presence of aggregates of single-walled and / or double-walled carbon nanotubes having a size greater than 10 μm is evident in another characteristic of the dispersion of single-walled and / or double-walled carbon nanotubes and HNBR, which is the rapid separation of the dispersion under oscillatory shear strain in a narrow slot channel having a size comparable to the aggregate size. Thus, the dispersion preferably has the ability to separate into a solvent with a low content of single-walled and / or double-walled carbon nanotubes and a high concentration gel of single-walled and / or double-walled carbon nanotubes and HNBR under oscillatory shear strain in a cone-and-plate rheometer cell, for example, at a frequency of 1 Hz and a relative shear strain amplitude of 100%, in a cone-and-plate rheometer cell with a cone angle of 1°.
[0035] In addition to single-walled and / or double-walled carbon nanotubes, the dispersion may contain impurities of other carbon allotropes, including, but not limited to, amorphous carbon and / or graphite and / or multi-walled carbon nanotubes. The effect of these impurities on the dispersion rheology is minor and therefore the impurities do not affect the technical results.
[0036] The dispersion of single-walled and / or double-walled carbon nanotubes and / or their aggregates may contain impurities of Group 8-11 metals or metal carbides used as catalysts in the production of carbon nanotubes, such as iron or cobalt, or other metals, bimetallic particles, or alloys thereof, which result from the method by which these carbon nanotubes are obtained. In some embodiments, including the production of a cathode slurry and further production of a cathode, the content of Group 8-11 metal impurities in the single-walled and / or double-walled carbon nanotubes and / or their aggregates is preferably less than 1 wt. %. In some embodiments, the content of Group 8-11 metal impurities in the single-walled and / or double-walled carbon nanotubes and / or their aggregates is more preferably less than 0.1 wt. %. In other embodiments, on the contrary, there is no reason to so limit the content of Group 8-11 metal impurities, and their content in the single-walled and / or double-walled carbon nanotubes and / or their aggregates can be up to 15 wt. %.
[0037] For the best synergistic effect to achieve the minimum flow behavior index n, the surface of the single-walled and / or double-walled carbon nanotubes preferably contains functional groups. In some embodiments, the single-walled and / or double-walled carbon nanotubes preferably contain carbonyl and / or hydroxyl and / or carboxyl groups on their surface. For other embodiments, the carbon nanotubes preferably contain chlorine-containing groups on the surface, but without being limited to the examples given. In this case, the interaction between the carbon nanotubes and the acetonitrile units of the rubber molecules is stronger and the synergistic effect with HNBR nanotubes for a lower flow behavior index is most pronounced. The functional groups can be generated on the surface of the carbon nanotubes by various methods known in the art. For example, carboxyl functional groups can be generated on the surface of the carbon nanotubes by heat treatment in a nitric acid solution, and chlorine-containing functional groups can be generated by one of the methods described in Russian Patent No. 2717516, but without being limited to the examples given. The method for functionalizing the carbon nanotubes is not the subject of the present invention. The content of functional groups on the surface of the single-walled and / or double-walled carbon nanotubes is preferably at least 0.1% by weight. In some embodiments, the single-walled and / or double-walled carbon nanotubes preferably contain at least 0.1% by weight of carbonyl and / or hydroxyl and / or carboxyl groups on their surface. The most preferred content of chlorine on the surface of the single-walled and / or double-walled carbon nanotubes is at least 0.1% by weight. However, the technical result can also be achieved with single-walled and / or double-walled carbon nanotubes that do not contain functional groups on the surface, for example, that have been intentionally heated in an inert atmosphere to remove potential functional groups on the surface.
[0038] The choice of solvent depends on the requirements for the subsequent application of the dispersion. For example, the dispersion solvent may be an organic solvent such as N-methyl-2-pyrrolidone, ethylene carbonate, tetrahydrofuran, dimethyl sulfoxide, dimethylacetamide, or a mixture thereof, but is not limited to the given examples, or a solution of two or more solvents, and an aqueous solution of an organic solvent. Also, from the viewpoint of the safety of the production and operation of the dispersion, it is preferred that the flash point of the solvent is at least 70°C to ensure the safe production and operation of the dispersion. In some embodiments, the flash point of the organic solvent is preferably at least 80°C, such as N-methyl-2-pyrrolidone (flash point of 89°C) or dimethylacetamide (flash point of 87°C), or other solvents, but is not limited to the given examples.
[0039] Dispersions containing a solvent, HNBR and single- and / or double-walled carbon nanotubes are pseudoplastic and are characterized by a very strong dependence of the dispersion viscosity on the shear rate in the flow due to the synergistic interaction of the single- and / or double-walled carbon nanotubes and the HNBR in the dispersion. This solves the technical problem in most applications, where on the one hand it is necessary to ensure a high viscosity of the undisturbed dispersion (during storage and / or transportation) and on the other hand it is necessary to ensure the necessary viscosity under the specific dispersion use conditions when the dispersion flows through a pipe or when the dispersion is sprayed through a nozzle or in other applications with a given shear rate in the flow. To solve this problem, the value of the fluid behavior index n is sufficiently small, not more than 0.37, and the flow consistency index K is at least 3.2 Pa·s n It is preferable that the value of the flow behavior index n is 0.30 or less. It is most preferable that the value of the flow behavior index n is 0.2 or less.
[0040] The flow behavior index n and the flow consistency index K are the dynamic dispersion viscosity μ as a function of shear rate γ, as described by the Ostwald-de Waele equation (1) above. effIt is important to note that the dependence of the dispersion viscosity as a function of the shear rate does not have to follow exactly the Ostwald-de Waele power law. If the behavior of the dispersion viscosity as a function of the shear rate differs from the power law, the flow behavior index n and the flow consistency index K are considered as the parameters that correspond to the best linear approximation on the curve of the logarithm of viscosity as a function of the logarithm of the shear rate, for example based on the least squares criterion.
[0041] The values of the flow behavior index n and the flow consistency index K preferably satisfy the following condition: n<1.25·lg(K / (Pa·s n ))-0.628. In this case, the viscosity of the undisturbed dispersion during storage is 1 / 6.3s -1 The shear rate remains high at above 20 Pa·s at shear rates below 20 Pa·s, allowing long-term storage and / or transportation of the dispersion without aggregation and / or settling of the carbon nanotubes and their aggregates.
[0042] The values of the flow behavior index n and the flow consistency index K preferably satisfy the following condition: n<1.24-0.787·lg(K / (Pa·s n In this case, the dispersion viscosity in the flow is 18.6s -1 At shear rates above 2 Pa·s, the viscosity is low enough to process this dispersion, including for the preparation of cathode slurries.
[0043] Another approach to describe the viscous properties of a fluid is to measure the complex modulus G*, and the real component of the storage modulus G', and the apparent component of the loss modulus G" under oscillatory shear strain. These values are usually measured in a thermostated plate-and-plate cell at a temperature of 20 + / - 1 °C, or more preferably in a cone-and-plate cell, since the latter provides the same shear rate throughout the entire volume of the cell. For a cone with an angle of 1°, a cone oscillation of 1° to the plane with a frequency of 1 Hz provides a shear strain amplitude of 100% and a shear strain amplitude of 1 s. -1 As mentioned above, the dispersion is subjected to a shear rate of 1s to achieve the technical result. -1 Less than, e.g. (1 / 6.3)s-1 The dispersions must be non-ideal pseudoplastic viscoelastic fluids with a dynamic viscosity of more than 20 Pa·s at a steady shear rate of 100 Hz. These shear rate values correspond to a shear strain amplitude of less than 16% at an oscillatory frequency of 1 Hz. Unfortunately, for dispersions containing carbon nanotubes, it is not possible to establish a direct correspondence between the dynamic viscosity under steady flow conditions and the components of the complex modulus determined in an oscillatory system. However, it is clear that a larger loss modulus G” means a higher viscosity and that for a dispersion to be characterized as a viscoelastic fluid, the phase angle δ=arctan(G” / G') must be greater than 15°, preferably greater than 18°. In this regard, the dispersions must have a loss modulus of more than 27 Pa at an oscillatory shear strain with a frequency of 1 Hz and a relative shear strain amplitude in the range of 5-10% in a cone-and-plate rheometer cell, and a dynamic viscosity of more than 18 Pa at an oscillatory shear strain with a frequency of 1 Hz and a relative shear strain amplitude in the range of 5-10% in a cone-and-plate rheometer cell. o It is preferably characterized by a phase angle exceeding
[0044] A method is disclosed for producing a dispersion containing a solvent in which the majority of the molecules are electrically neutral, 0.2-2 wt. % single-walled and / or double-walled carbon nanotubes, and hydrogenated nitrile butadiene rubber, with a weight ratio of single-walled and / or double-walled carbon nanotubes to hydrogenated nitrile butadiene rubber of at least 0.1 and not more than 10, the method comprising a series of at least three dispersion stages (D) and at least two alternating rest stages (R), wherein any one of the dispersion stages (D) is at least 10,000 s -1 or ultrasonicating the dispersion at a frequency of at least 20 kHz with a specific input energy of at least 1 W h / kg, wherein the resting phase (R) is a phase in which the dispersion between two successive dispersion phases (D) is stirred for at least 1 min for 10 s -1 The sample is exposed to a shear rate of less than 100 .mu.m.
[0045] The disclosed method for producing a dispersion allows, on the one hand, to disperse the single-walled carbon nanotubes due to the high shear rate in step (D) and, on the other hand, to form a separated structure of a two-component self-sorting gel containing gel regions with mainly HNBR and solvent, interconnected in a single network by single-walled and / or double-walled carbon nanotubes in the stationary step (R). It should be noted that this production method ensures a better dispersion and distribution of the single-walled and / or double-walled carbon nanotubes. The obtained dispersion is pseudoplastic during the mechanical processing or ultrasonic treatment, so that localized regions with low viscosity in areas with high shear rates and localized regions with high viscosity in areas with low shear rates are formed, with a weight transfer between these regions being of low strength or almost impossible. For this reason, in the proposed method, in order to achieve the technical result, the mechanical processing or ultrasonic treatment steps must be repeated more than twice, and between the cyclically repeated steps of mechanical processing or ultrasonic treatment, the dispersion must be left undisturbed for at least 1 min or must be left undisturbed for at least 10 s. -1 The shear rate must be relatively low, less than 100 rpm.
[0046] Mechanical processing can be carried out using a variety of dispersing or mixing equipment that provides the desired shear rate in the dispersion stream, including, for example, rotor-stator dispersers and homogenizers (dissolvers), colloid mills, bead mills, planetary mills, high-pressure homogenizers (HPH), and rotary pulsating apparatus (RPA). In some embodiments, disk dissolvers, i.e., vertical agitators with disk impellers, preferably with toothed disk impellers (cutters), are sufficient for mechanical activation and are preferred. When using a bead mill or high-pressure homogenizer with a dispersion stream passing through a very high shear rate zone, the dispersion stage (D) includes forcing the entire volume of the dispersion into the mill or homogenizer. In this case, the stationary stage (R) includes the step of forcing the dispersion mixture, including the solvent, HNBR, and single-walled and / or double-walled carbon nanotubes, into the tank during the dispersion cycle and for 10 s. -1 This means that the mixture is only slowly stirred at a shear rate less than 100 rpm.
[0047] The choice of equipment for mechanical or ultrasonic processing, the specific power, the duration of the treatment at each stage depends on the available equipment and the composition of the dispersion, i.e. the selected solvent, the concentration of carbon nanotubes, the concentration and grade of selected HNBR, and the availability of other fillers and additives. In this regard, some equipment options may not apply to some dispersion compositions.
[0048] In some cases, the method preferably includes a series of at least five alternating dispersion stages (D) and at least four stationary stages (R), any one of the dispersion stages (D) lasting at least 10000 s with a specific input energy of at least 10 W·h / kg. -1 or ultrasonicating the dispersion at a frequency of at least 20 kHz with a specific input energy of at least 1 W·h / kg, and the stationary phase (R) is a step of suspending the dispersion between two successive dispersion phases (D) for at least 1 min, for 10 s. -1 In another embodiment, the method preferably comprises a series of at least 10 alternating dispersion stages (D) and at least 9 stationary stages (R). In another embodiment, the method preferably comprises a series of at least 30 alternating dispersion stages (D) and at least 29 stationary stages (R).
[0049] In some embodiments, one or several devices provide a mechanical processing or ultrasonic treatment step and the dispersion is held for 10 s. -1 A series of at least three dispersion stages (D) and at least two stationary stages (R) are alternately carried out by circulating the dispersion between a slowly stirred tank at a shear rate of less than 1000 rpm, where the factor of such dispersion circulation during dispersion production is preferably at least 5. In some process embodiments, the dispersion circulation factor during production can be at least 10. In other embodiments, the dispersion circulation factor during production is preferably at least 30. The preferred number of circulation cycles is defined by the composition of the dispersion, the type of dispersion equipment, and the specific input power at the dispersion stage.
[0050] In some embodiments, the production process preferably comprises a circulation rate of 100 to 10,000 kg / h and a specific input energy of at least 10 W·h / kg for at least 10,000 s -1 The ultrasonic processing device is equipped with a rotational pulsating device at a shear rate of 10 s, a frequency of at least 20 kHz and an immersion sonotrode (ultrasonic probe, ultrasonic activator) at a specific input energy of at least 1 W·h / kg, and the dispersion is held for at least 1 min for 10 s. -1 The method includes circulating the dispersion between a tank that is slowly stirred at a shear rate of less than 20,000 s. Residence time refers to the ratio of tank volume to circulation rate, i.e., the average time that the dispersion is in the tank in the approximation of an ideal mixing device. In some embodiments, the shear rate between the rotor and stator of the rotary pulsating device is preferably at least 20,000 s. -1 , most preferably at least 50000s -1 In some embodiments, the specific input energy when the dispersion passes through the rotary pulsating device is preferably 30 W·h / kg or less. However, technical results are also achievable with specific input energies of 10-30 W·h / kg when the dispersion passes through the rotary pulsating device. Also preferably, the ultrasonic treatment is carried out at a frequency of at least 40 kHz and a specific input energy of more than 2 W·h / kg. However, technical results are also achievable with frequencies of 20 kHz-40 kHz and specific input energies of 1-2 W·h / kg, but this requires more cycles.
[0051] In some embodiments, the manufacturing process preferably comprises at least 10,000 s -1 and a specific input energy of at least 10 W·h / kg, and the dispersion is held in the tank for an average residence time of at least 1 minute for 10 s -1The method includes circulating the dispersion at a circulation rate of 100 to 10,000 kg / h between a tank that is slowly stirred at a shear rate of less than 10000 s. The pressure upstream of the disperser valve can be more than 30 MPa, for example more than 60 MPa, and is determined by the design of the disperser. The nozzle diameter is also determined by the design of the disperser, which is outside the scope of the present invention, and can be less than 2 mm, for example 700 μm. In some embodiments, the shear rate in the disperser is preferably at least 70,000 s. -1 and most preferably 500000s -1 In some embodiments, the specific input energy at each dispersion stage is preferably greater than 20 W·h / kg, most preferably greater than 30 W·h / kg. However, technical results can also be achieved with a specific input energy at each dispersion stage between 10 and 20 W·h / kg of dispersion, but this would require more cycles.
[0052] A method for producing a cathode slurry containing an active material, a solvent, hydrogenated nitrile butadiene rubber, and at least 0.005 wt. % single-walled and / or double-walled carbon nanotubes is disclosed, the method comprising: (1) mixing a lithium-containing active material, a solvent in which most of the molecules are electrically neutral, the hydrogenated nitrile butadiene rubber, and the dispersion containing the single-walled and / or double-walled carbon nanotubes, the content of the single-walled and / or double-walled carbon nanotubes in the dispersion being 0.2-2 wt. %, and the weight ratio of the single-walled and / or double-walled carbon nanotubes to the hydrogenated nitrile butadiene rubber in the dispersion being at least 0.1 and not more than 10; and (2) stirring the resulting mixture to produce a uniform slurry.
[0053] Disclosed is a cathode slurry containing an active material, a solvent, hydrogenated nitrile butadiene rubber, and single-walled and / or double-walled carbon nanotubes, the cathode slurry containing at least 0.005 wt% single-walled and / or double-walled carbon nanotubes and produced by the above method. The cathode slurry preferably contains at least 0.01 wt% single-walled and / or double-walled carbon nanotubes.
[0054] In step (2), the stirring of the mixture obtained in step (1) to produce a uniform suspension can be performed by any known mixing method with any mixing equipment, such as, but not limited to, a vertical stirrer (also known as a dissolver), a planetary mixer, a rotor-stator type mixer, a twin screw mixer. In some embodiments, the stirring is preferably performed using a disk dissolver, i.e., a vertical stirrer with a disk impeller, preferably with a toothed disk impeller (cutter). In step (2), a planetary mixer is most preferred. It should be noted that the choice of the mixing method for step (2) and the choice of equipment for this step are outside the scope of the present invention.
[0055] Cathode slurry active material refers to any lithium-containing material suitable as a cathode active material, i.e., a material that has the following properties (reviewed by MS Wittingham, Lithium Batteries and Cathode Materials, Chem. Rev. 2004, Vol. 104, pp. 4271-4301): (1) the material contains easily reducible / oxidizable ions, e.g., transition metal cations; (2) the material reacts with lithium reversibly without fundamental change in its structure; (3) the material reacts with lithium with a high free energy of reaction (Helmholtz potential); (4) the material interacts with lithium very rapidly. For example, cathode slurry active materials include LiTiS2, LiVSe2, LiCoO2, LiNiO2, LiFePO4 (also called LFP), LiNi x Mn y Co z O2 (where x, y, and z are positive numbers less than 1, and x+y+z=1, also known as NMC, e.g. LiNi 0.8 Mn 0.1 Co 0.1 O2 may be NMC 811, or any other, but not limited to the examples given, or a mixture thereof.
[0056] The simultaneous presence of single-walled and / or double-walled carbon nanotubes and HNBR in the cathode slurry results in a significant difference in the rheological properties of the slurry from an ideal (Newtonian) fluid, due to similar synergistic effects as described above for the dispersions, which is expressed in the fact that the cathode slurry has a low value of the flow behavior index n, which is preferably at least 10 Pa s n The flow consistency index K is less than 0.3, which means that the cathode slurry has, on the one hand, a very low viscosity, e.g., a viscosity of 100 s, which is typical for the subsequent application of the cathode slurry to the conductive electrode plate. -1 At shear rates above 1 Pa s, on the other hand, high viscosities, e.g. -1 This combination of cathode slurry properties is preferred and solves the technical problem of providing high viscosity during storage prior to use (application to the cathode current collector), providing high viscosity after application to the current collector without spreading to ensure good quality of the edges of the cathode active material layer, and at the same time providing a low viscosity of the cathode slurry under defined processing conditions for application to the current collector.
[0057] The cathode slurry may contain one or several organic solvents or aqueous solutions of organic solvents. Among the organic solvents, N-methyl-2-pyrrolidone is the most preferred, but other solvents such as ethylene carbonate, tetrahydrofuran, dimethylsulfoxide, dimethylacetamide, etc. may also be used, but are not limited to the given examples. Obviously, the cathode slurry should contain the solvents contained in the dispersion, i.e. the solvent in which most of the molecules are electrically neutral, HNBR, and the single-walled and / or double-walled carbon nanotubes used to produce the cathode slurry. However, the cathode slurry may further contain another solvent if it offers some advantage from the viewpoint of the technological process. The additional solvent, chemically similar to the one in the dispersion or different, may be added in step (1) of mixing the lithium-containing cathode active material with the dispersion containing the single-walled and / or double-walled carbon nanotubes and HNBR, or in an additional mixing step preceding the mixing step (1), or in a separate mixing step after the mixing step (1) and before the step (2).
[0058] To ensure the necessary plasticity and strength of the cathode material after drying, binders can be further added to the cathode slurry. These additives, which are most typically polymeric materials, can be introduced in the form of a solution or suspension, for example an aqueous suspension, a suspension based on N-methyl-2-pyrrolidone or another solvent, the choice of the solvent depending on the characteristics of the technological process used. These additives can include, for example, suspensions of fluoroplastics, latexes of various rubbers, polyacrylic acid or its salts, for example Na or Li salts. Hydrogenated nitrile butadiene rubber of the same grade as the dispersion, or a different one, can be added as a binder to the cathode slurry. The binder can be added in step (1) of mixing the lithium-containing cathode active material with the dispersion containing single-walled and / or double-walled carbon nanotubes and HNBR, or in an additional mixing step preceding mixing step (1), or in a separate mixing step after mixing step (1) and before step (2).
[0059] In order to achieve the technical result, it is important that the dispersion used to prepare the slurry in step (1) contains both HNBR and single-walled and / or double-walled carbon nanotubes, i.e. it is not sufficient that the dispersion used to prepare the slurry contains single-walled and / or double-walled carbon nanotubes and that HNBR is added thereto during the preparation of the cathode slurry.
[0060] To summarize the above, in some embodiments, the cathode slurry manufacturing process preferably includes one or more additional steps of mixing with a solvent and / or one or more binders and / or conductive additives prior to step (2). In some embodiments, a solvent and / or one or more binders and / or conductive additives are also preferably added to the mixture in the mixing step (1).
[0061] The weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the cathode slurry is preferably at least 0.05 and not more than 10. In some embodiments, the weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the cathode slurry is preferably at least 0.1 and not more than 5. The most preferred weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the cathode slurry is at least 0.33 and not more than 3. However, synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the cathode slurry ranging from 0.03 to 0.33. In some embodiments, the most preferred weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the cathode slurry is at least 0.5 and not more than 2. Synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR in the cathode slurry ranging from 2 to 10.
[0062] In some embodiments, the cathode slurry preferably further contains, but is not limited to, at least 0.01 wt. % of conductive additives other than single-walled and / or double-walled carbon nanotubes, such as graphite, carbon black, acetylene black, carbon fibers of various morphologies, thicknesses and lengths, such as multi-walled carbon nanotubes, or metal particles, for example, such additives can ensure another advantage of reducing the internal resistance of the cathode.
[0063] The cathode slurry may contain Group 8-11 metal particles that are impurities in the single-walled and / or double-walled carbon nanotubes from the carbon nanotube manufacturing process. These conductive additives containing metal particles do not prevent the achievement of the technical result. However, it is noted that metal particles are undesirable in most embodiments, and the content of Group 8-11 metal impurities in the cathode slurry is preferably less than 1% by weight of the single-walled and double-walled carbon nanotubes. Some applications prefer the content of Group 8-11 metal impurities in the cathode slurry to be less than 0.1% by weight of the content of the single-walled and double-walled carbon nanotubes.
[0064] The present invention provides a method for producing a cathode for a lithium-ion battery, characterized in that the method comprises a series of steps for producing the cathode slurry: (1) mixing the dispersion containing the lithium-containing active material and a solvent in which most of the molecules are electrically neutral, hydrogenated nitrile butadiene rubber, and single- or double-walled carbon nanotubes, (the content of single- and / or double-walled carbon nanotubes in the dispersion is 0.2-2 wt %, and the weight ratio of single- and / or double-walled carbon nanotubes to hydrogenated nitrile butadiene rubber in the dispersion is at least 0.1 and not more than 10), (2) stirring the resulting mixture to produce a homogeneous slurry, (3) applying the resulting slurry to a current collector, (4) drying the applied slurry until a cathode is formed, and (5) compressing the cathode to the required density. The method of making the cathode can include an additional step of introducing a binder and / or additional solvent that is chemically similar to or different from that in the dispersion, which can be added in the step of (1) mixing the lithium-containing cathode active material with the dispersion containing single-walled and / or double-walled carbon nanotubes and HNBR, or can be added in a separate mixing step preceding mixing step (1), or can be added in a separate mixing step after mixing step (1) and before step (2).
[0065] The present invention provides a cathode for a lithium-ion battery, which is characterized by being produced by a method including a series of steps for producing the cathode slurry: (1) mixing the dispersion containing a lithium-containing active material and a solvent in which most of the molecules are electrically neutral, hydrogenated nitrile butadiene rubber, and single-walled or double-walled carbon nanotubes (the content of single-walled and / or double-walled carbon nanotubes in the dispersion is 0.2-2 wt %, and the weight ratio of single-walled and / or double-walled carbon nanotubes to hydrogenated nitrile butadiene rubber is at least 0.1 and not more than 10), (2) stirring the resulting mixture to produce a uniform slurry, (3) applying the resulting slurry to a current collector, (4) drying the applied slurry until a cathode is formed, and (5) compressing the cathode to a required density.
[0066] The simultaneous presence of HNBR and single-walled and / or double-walled carbon nanotubes in the cathode slurry influences the viscosity dependency on shear rate, ensuring both stability and moderate viscosity of the cathode slurry under the application conditions to the current collector, and lithium-ion batteries with the cathode of the present invention exhibit very stable operation in successive charge-discharge cycles. For example, the battery capacity after 400 charge-discharge cycles at a rate of 1C can be more than 80%, in some embodiments more than 90%, and in some embodiments more than 95% of the initial battery capacity. The achievable battery stability depends on the active material in the battery cathode and the battery anode.
[0067] The present invention is illustrated by the accompanying figures and examples, which are provided for illustrative purposes only and are not intended to limit the possible embodiments of the present invention. For convenience, basic information regarding the examples is also summarized in tables providing information on the composition and properties of the dispersions. [Brief description of the drawings]
[0068] [Figure 1] 1 shows transmission electron micrographs of Tuball™ single-walled carbon nanotubes in dispersions of Examples 1 and 4 and Comparative Example 9. [Diagram 2] FIG. 1 shows dynamic light scattering data for the distribution of the volume fraction (%) of particles (nanotubes and their bundles) by hydrodynamic diameter Dh (nm) in the dispersions of Example 1 (circles), Example 2 (triangles) and Example 5 (squares). [Diagram 3] FIG. 1 shows the dependence of the dynamic viscosity (Pa s) of dispersions of solutions of Example 1 (circles), Example 2 (squares), Example 3 (diamonds), Comparative Example 8 (dark triangles) and Comparative Example 9 (light triangles, these values are multiplied by 100 for ease of presentation) on shear rate (s-1). [Figure 4] 1 shows the dependence of the kinetic viscosity (Pa·s) of the cathode slurries of Example 1 (circles), Example 2 (squares), Example 3 (diamonds), and Comparative Example 8 (dark triangles) on the shear rate (s-1). [Diagram 5] Photographs of the slurry layers applied to the current collectors of Example 1 (left) and Comparative Example 9 (right) are shown. [Figure 6] 1 shows the dependence of capacity related to the initial capacity (%) on the number of charge / discharge cycles (charge rate 1C, discharge rate 1C) of a lithium ion battery having a cathode of Example 1. [Figure 7] 1 shows the dependence of capacity in terms of initial capacity (%) on the number of charge-discharge cycles (charge rate 1C, discharge rate 1C) of lithium ion batteries having the cathodes of Examples 2 and 3. [Figure 8] 1 shows a transmission electron microscope photograph of single-walled and double-walled carbon nanotubes of the dispersion of Example 3. [Figure 9] 4 shows the dependence of capacity in terms of the initial capacity (%) on the number of charge-discharge cycles (charge rate 0.5C, discharge rate 1C) of a lithium ion battery having a cathode of Example 4. [Figure 10] Figure 2 shows the separation of the dispersion from Example 5 when subjected to an oscillatory shear strain with 100% amplitude at a frequency of 1 Hz in a cone-and-plate rheometer cell (measurement plate on the left, measurement cone on the right, cone angle 1°). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0069] Example 1 The dispersion is ML (1+4) It contains 0.8% by weight of partially hydrogenated nitrile butadiene rubber Therban® 3496 with a viscosity of 55 Mooney units at 100 °C, the content of nitrile units is 34% by weight, the residual content of polybutadiene units is 18% by weight and the content of units obtained by hydrogenation of conjugated diene units is 48% by weight. The dispersion also contains 0.4% by weight of single-walled carbon nanotubes and their aggregates. N-methyl-2-pyrrolidone (NMP) was used as the solvent. The single-walled carbon nanotubes used to prepare the dispersion are Tuball® SWCNTs. The diameter of the SWCNTs ranges from 1.2 to 2.1 nm, with an average diameter of 1.54 nm (the diameter was determined by TEM of the dried suspension and the absorption band S in the optical absorption spectrum of the suspension). 1-1 Raman spectroscopy at 532 nm reveals a peak at approximately 1580 cm, typical of single-walled carbon nanotubes. -1 Strong G lines at around 1330 cm and other allotropic forms of carbon and defects in single-walled carbon nanotubes. -1 The G / D line intensity ratio is 80.5. The specific surface area determined from the nitrogen adsorption isotherm is 1220 m 2 / g. See FIG. 1 for a transmission electron micrograph of the SWCNTs used. The SWCNTs for producing the dispersion were further modified with chlorine by the method described in Russian Patent No. 2717516. Energy dispersive spectroscopy shows that the chlorine content in the tubular SWCNTs is 0.25 wt. %. %. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) shows that the SWCNTs contain 0.46 wt. % iron impurity. The weight ratio of single-walled carbon nanotubes to HNBR is 0.5.
[0070] Mix NMP, HNBR and SWCNT in the required proportions and disperse them in a Chaoli GJB500 high-pressure homogenizer (D) and a gate agitator for about 2 s. -1The dispersion was prepared by repeating eight times alternating stages of standing in a 65 liter tank with slow stirring at a shear rate of 1000 rpm and 1000 rpm. The dispersion was carried out at a pressure of 60 MPa, a dispersion transfer flow rate of 300 kg / h, and a shear rate of approximately 2.3·10 5 s -1 The shear rate in the homogenizer valve nozzle was 1.0 MPa. The measured power consumption was 16 kW, and the specific input energy in stage (D) was about 53 W·h / kg. The tank residence time of the dispersion in stage (R) was about 13 min.
[0071] The size distribution of the number of carbon nanotube bundles was determined by dynamic light scattering (DLS) of a dispersion diluted in water to a SWCNT concentration of 0.001 wt %. The hydrodynamic diameter distribution of the volume fraction of particles (nanotubes and their aggregates) in the dilute dispersion obtained by DLS using a Malvern Zetasizer ZS device is shown by the round curve in Figure 2. Figure 2 shows that the size distribution of the volume fraction of nanotubes and their aggregates is bimodal, with hydrodynamic diameters in the ranges of 100-1000 nm and 4-7 μm. The first and most intense maximum is at D hm = 380 nm, and the second mode D h2m is approximately 5 μm.
[0072] Complex modulus measurements performed with an Anton Paar MCR302 rheometer on a cone-and-plate cell with a cone angle of 1° and an oscillation frequency of 1 Hz showed that at oscillation amplitudes ranging from 0.05 to 0.1°, corresponding to shear strains of 5–10%, the loss modulus G” was 53–75 Pa, implying a high viscosity of the dispersion at relative rest, and the phase angle was 27.5°, characterizing the dispersion as a viscoelastic nonideal fluid.
[0073] The dispersion is subjected to shear rate (s -1The viscosity is characterized by the viscosity (Pa s) as a function of shear rate. The viscosity was measured at a constant temperature of 25 °C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The dependence of the viscosity on the shear rate is 0.093 s -1 ~47s -1 The flow behavior index n is 0.15 and the flow consistency index is 22.5 Pa s 0.15 1 / 6.3s -1 The dispersion viscosity in the low shear rate region is greater than 100 Pa s and is 18.6 s -1 For shear rates above 100s, the shear rate is less than 1.95 Pa s. -1 A dispersion viscosity of 0.8 Pa·s can be estimated at a shear rate of 0.
[0074] The main dispersion parameters are given in the summary table.
[0075] The dispersion was used to prepare a cathode slurry containing 98.83 parts by weight of the active material LiNiCoAlO2 (NCA), 29.82 parts by weight of NMP solvent, 1 part by weight of polyvinylidene fluoride binder, 1 part by weight of acetylene black, 0.12 parts by weight of Arlanxeo hydrogenated nitrile butadiene rubber, and 0.06 parts by weight of single-walled carbon nanotubes.
[0076] The cathode slurry was prepared by the following sequence of steps: - adding 10 g of a solution containing 1 g Solef 5130 polyvinylidene fluoride (PVDF) binder and 9 g NMP to 15 g of dispersion and mixing for 30 minutes on an overhead stirrer - adding additional binder and solvent performed prior to step (1); - Mix the resulting mixture with 98.83 g of active material LiNiCoAlO2 (NCA) for 30 minutes - step (1); - 1 g of acetylene black and a further 6 g of NMP solvent are added to the resulting mixture - an additional step of adding a conductive additive and a solvent, carried out after step (1); - Stir for 16 hours to produce a homogenous slurry - Step (2).
[0077] Due to the presence of both single-walled carbon nanotubes and HNBR, the resulting cathode slurry also has a sharp and significant dependence of viscosity on shear rate, as shown by the circles (curve 1) in Figure 4. The flow behavior index n is 0.19 and the flow consistency index is 33.1 Pa s 0.16 The dependence approximation is -1 This allows the estimation that the shear rate is less than 0.8 Pa s at a shear rate of 1 s, which provides the process capacity for application to the current collector plate. -1 At shear rates below 100°C, the viscosity exceeds 33 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.
[0078] The stability of the slurries during storage was determined by the change in the distribution of the solid particle content along the height of the slurry layer after storage of the slurries in 50 ml cylindrical test tubes with a diameter of 30 mm. For this purpose, the slurries were placed in test tubes, closed with lids and kept under standard conditions (atmospheric pressure, 25 ° C) for 7 days. The upper, middle and lower thirds of the test tubes were then sampled with a pipette and the weight fraction of the solvent and solid non-volatile components in the samples was determined by drying. For the cathode slurry of this example, the solvent content in the initial slurry was 22.8 wt.%, and after one week of storage, the solvent content was 23.2 wt.% in the lower third, 22.7 wt.% in the middle and 22.5 wt.% in the upper third. The difference with the initial solvent content did not exceed 2. relative%, which is significantly smaller than the slurry described in Comparative Example 8 below, indicating the high stability of the resulting slurry. The slurry can be used to manufacture cathodes after 7 days of storage.
[0079] The lithium-ion battery cathode was prepared by applying the resulting slurry to a current collector (step 3), drying the applied slurry until a cathode was formed (step 4), and applying a 3.8 g / cm 2The cathode slurry was fabricated by compressing it to the required density of 10 ...
[0080] From the resulting cathode and anode having silicon monoxide as the active material, 4.3 mg / cm 2 A lithium-ion battery was assembled with a load of 1000 mA. A polypropylene separator with a thickness of 25 μm was used. A 1.2 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with the addition of 10% v / v fluoroethylene carbonate was used as the electrolyte. The initial battery capacity at a discharge rate of 0.1 C was 1500 mA·h. The dependence of the capacity (referred to as the initial capacity) on the number of charge-discharge cycles (charge current 1500 mA, discharge current 1500 mA) is shown in Figure 6. The battery capacity is 86% of the initial capacity after 400 cycles and 80% of the initial capacity after 800 cycles.
[0081] The resulting high stability of the final battery product during charge-discharge cycling confirms the achieved technological results, at the dispersion level, i.e., dispersion stability combined with processability in the cathode slurry manufacturing process, at the cathode level, i.e., cathode slurry stability (no peeling) and processability when applied to the current collector (including smooth edges of the coating without material spreading on the current collector), i.e., high quality of the cathode, high specific capacity and high stability during cycling.
[0082] EMBODIMENTS OF THE PRESENT DISCLOSURE Example 2 The dispersion is ML (1+4)It contains 0.6 wt. % of low viscosity hydrogenated nitrile butadiene rubber Therban® 3404 with a viscosity of 39 Mooney units at 100°C, the content of nitrile units is 34 wt. %, the residual content of polybutadiene units is less than 0.9 wt. %, and the content of hydrogenated polybutadiene units is 65 wt. %. The dispersion also contains 0.4 wt. % of single-walled carbon nanotubes and their aggregates. The solvent is N-methyl-2-pyrrolidone (NMP), which is an organic solvent with a flash point of 89°C. The single-walled carbon nanotubes used to prepare the dispersion are Tuball™-99 SWCNTs. The diameter of the SWCNTs ranges from 1.2 to 2.1 nm, with an average diameter of 1.58 nm (the diameter was determined by TEM of the dried suspension, the absorption band S in the optical absorption spectrum of the suspension). 1-1 Raman spectroscopy at 532 nm revealed a peak at 1580 cm typical of single-walled carbon nanotubes. -1 Strong G lines at around 1330 cm and other allotropic forms of carbon and defects in single-walled carbon nanotubes. -1 The G / D line intensity ratio is 56. The specific surface area determined from the nitrogen adsorption isotherm is 1160 m 2 / g. Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) shows that the SWCNTs contain 0.4 wt% Fe (group 8 metal) impurity. The weight ratio of SWCNTs to HNBR in the slurry is 0.667.
[0083] Dispersions were prepared by mixing the required proportions of NMP, HNBR, and SWCNTs and dispersing 10-fold in a NETZSCH Omega 500 high-pressure homogenizer at a pressure of 65 MPa and a dispersion transfer rate of 300 kg / h (Step D). The estimated shear rate in the nozzle was approximately 9·10 5 s -1 The power consumption was 8 kW, and the specific input energy in stage (D) was about 27 W·h / kg. Between each of the two dispersion stages (D), the dispersion was placed in a 50 L tank and stirred for about 1 s by a gate agitator. -1 The mixture was stirred slowly for 10 minutes at a shear rate of 100 rpm (Stage R).
[0084] The number size distribution of carbon nanotube bundles was determined by dynamic light scattering (DLS) of a dispersion diluted in water to a SWCNT concentration of 0.001 wt %. The hydrodynamic diameter distribution of the volume fraction of particles (nanotubes and their aggregates) in the dilute dispersion obtained by DLS using a Malvern Zetasizer ZS device is shown by the triangular curve in Figure 2. Figure 2 shows that the size distribution of the volume fraction of nanotubes and their aggregates is bimodal, with hydrodynamic diameters in the ranges of 100-1000 nm and 4-8 μm. The first and most intense maximum is at D hm = 500 nm, and the second mode D h2m is approximately 6.5 μm.
[0085] The dispersions were subjected to shear rate (s -1 It is characterized by its viscosity (Pa s) as a function of temperature. The flow behavior index n is 0.22 and the flow consistency index is 15.3 Pa s 0.22 1 / 6.3s -1 The dispersion viscosity at low shear rates is greater than 65 Pa s and is less than 18.6 s. -1 At shear rates above 100s, the shear rate is less than 1.54 Pa s. -1 A dispersion viscosity of 0.41 Pa·s can be estimated at a shear rate of 0.
[0086] Complex modulus measurements performed with an Anton Paar MCR302 rheometer on a cone-and-plate cell with a cone angle of 1° and an oscillation frequency of 1 Hz showed that at oscillation amplitudes ranging from 0.05° to 0.1°, corresponding to shear strains of 5–10%, the loss modulus G” was between 38° and 50 Pa, implying a high viscosity of the dispersion at relative rest, and the phase angle was between 23° and 25°, characterizing the dispersion as a viscoelastic nonideal fluid.
[0087] The main dispersion parameters are given in the summary table.
[0088] Using the dispersion, 75.3 wt. % of the active material LiNi 0.8 Mn 0.1 Co 0.1 A cathode slurry was prepared containing O2 (NMС811), 23.9 wt% NMP solvent, 0.79 wt% polyvinylidene fluoride binder, 0.012 wt% HNBR, and 0.008 wt% single-walled carbon nanotubes. The weight ratio of single-walled carbon nanotubes to HNBR is 0.67. The cathode slurry was prepared by the following sequence of steps: - adding 10 g of a solution containing 10 wt. % polyvinylidene fluoride (PVDF) in NMP to 2.53 g of the dispersion and mixing for 30 minutes on an overhead stirrer - adding additional binder and solvent carried out prior to step (1); - the resulting mixture is mixed with 95 g of active material NCM811 and an additional 18 g of NMP solvent - step (1); - Stir for 16 hours to produce a homogenous slurry - Step (2).
[0089] Due to the presence of both SWNTs and HNBR, the resulting cathode slurry also has a sharp and significant dependence of viscosity on shear rate, as shown by the squares in Figure 4. The flow behavior index n is 0.16 and the flow consistency index is 17.6 Pa s 0.16 It is 46.5s -1 The viscosity measured at a shear rate of 100 s was 0.69 Pa s. -1 Extrapolation of the shear rate dependence of gives a viscosity estimate of about 0.37 Pa s, which provides a process capacity for application to the current collector plate. -1 At shear rates below 100°C, the viscosity exceeds 17.6 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.
[0090] The stability of the slurries during storage was determined by the change in the distribution of the solid particle content along the height of the slurry layer after storage of the slurries in 50 ml cylindrical test tubes with a diameter of 30 mm. For this purpose, the slurries were placed in test tubes, closed with lids and kept under standard conditions (atmospheric pressure, 25 ° C) for 7 days. The upper, middle and lower thirds of the test tubes were then sampled with a pipette and the weight fractions of the solvent and solid non-volatile components in the samples were determined by drying. For the cathode slurry of this example, the solvent content in the initial slurry was 23.9 wt.%, and after one week of storage, the solvent content was 24.4 wt.% in the upper third, 23.7 wt.% in the middle and 23.5 wt.% in the lower third. The difference from the initial solvent content did not exceed 2 relative %, which is significantly smaller than the slurry described in Comparative Example 8 below, indicating a high stability of the resulting slurry.
[0091] The lithium-ion battery cathode was prepared by applying the resulting slurry to a current collector (step 3), drying the applied slurry until a cathode was formed (step 4), and applying a 3.7 g / cm 2 The cathode properties were determined by assembling a cell with a Li cathode and a Li reference electrode and an electrolyte of 1 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with additional 5% v / v vinyl carbonate. The initial specific capacity of the cathode at a discharge current of 0.02 A / g of the cathode material is 185 mA·h / g of the cathode material.
[0092] A lithium-ion battery was assembled from the obtained cathode and anode with graphite as the active material. A polypropylene separator with a thickness of 25 μm was used. A 0.8 M solution of LiPF6 in a 1:1:1 mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with the addition of 1% v / v vinyl carbonate was used as the electrolyte. The initial battery capacity at a discharge rate of 0.1 C was 1520 mA·h. The dependence of the capacity (referred to as the initial capacity) on the number of charge-discharge cycles (charge current 1500 mA, discharge current 1500 mA) is shown in the set of points 2 in Figure 7. The battery capacity exceeds 90% of the initial capacity after 500 cycles.
[0093] Example 3 The dispersion is similar to that described in Example 2, but contains a mixture of single-walled and double-walled carbon nanotubes with diameters between 1.2 and 2.8 nm and an average diameter of 1.8 nm (diameters were determined by TEM of the dried suspension and by the position of the radial breathing mode (RBM) lines in the Raman spectrum). The intensity ratio of the G / D lines in the Raman spectrum of light with a wavelength of 532 nm is 34. The availability of double-walled carbon nanotubes bundled together with single-walled carbon nanotubes is confirmed by the electron micrograph provided in FIG. 8. The concentration of carbon nanotubes in the dispersion is 0.4% by weight. The dispersion also contains 0.6% by weight of hydrogenated nitrile butadiene rubber Therban® 3406. The weight ratio of single-walled and double-walled carbon nanotubes to HNBR in the slurry is 0.667.
[0094] Dispersions were prepared by mixing the required proportions of NMP, HNBR, and a mixture of SWCNT and DWCNT and dispersing 32-fold in a NETZSCH Omega 500 high pressure homogenizer at a pressure of 65 MPa and a dispersion transfer rate of 300 kg / h (Step D). The estimated shear rate in the nozzle was approximately 9·10 5 s -1The power consumption was 8 kW, and the specific input energy in stage (D) was about 27 W·h / kg. Between each of the two dispersion stages (D), the dispersion was placed in a 50 L tank and stirred for about 1 s by a gate agitator. -1 The mixture was stirred slowly for 10 minutes at a shear rate of 100 rpm (Stage R).
[0095] The dispersion was analyzed by the shear rate (s -1 The viscosity was measured at a constant temperature of 25 °C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The viscosity dependence on shear rate was 0.093 s -1 ~46.5s -1 The flow behavior index n is 0.13 and the flow consistency index is 7.3 Pa s 0.13 1 / 6.3s -1 The dispersion viscosity at low shear rates is greater than 37 Pa s and is less than 18.6 s. -1 In the region of shear rates above 100, the shear strength is less than 0.6 Pa s.
[0096] Complex modulus measurements performed with an Anton Paar MCR302 rheometer on a cone-and-plate cell with a cone angle of 1° and an oscillation frequency of 1 Hz showed that at oscillation amplitudes ranging from 0.05 to 0.1°, corresponding to shear strains of 5–10%, the loss modulus G” was 35–40 Pa, implying a high viscosity of the dispersion at relative rest, and the phase angle was 20°–26°, which characterizes the dispersion as a viscoelastic nonideal fluid.
[0097] The main dispersion parameters are given in the summary table.
[0098] Using the dispersion, 73.9 wt. % of the active material LiNi 0.8 Mn 0.1 Co 0.1A cathode slurry was prepared containing O2 (NMС811), 25.2 wt% NMP solvent, 0.75 wt% polyvinylidene fluoride (PVDF) binder, 0.09 wt% hydrogenated nitrile butadiene rubber Therban® 3406, and 0.06 wt% single-walled and double-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - adding 100 g of a solution containing 6 g of polyvinylidene fluoride (PVDF) binder and 94 g of NMP to 120 g of the dispersion and mixing for 30 minutes on an overhead stirrer - a step of adding binder and solvent carried out prior to step (1); -The resulting mixture was mixed with 300 g of active material LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMС811) and stirred for 30 minutes, and 292.8 g of the active material LiNi 0.8 Mn 0.1 Co 0.1 Add O2 (NMС811) to the resulting mixture - stage (1); - Stir for 16 hours to produce a homogenous slurry - Step (2).
[0099] With both single-walled / double-walled carbon nanotubes as well as HNBR in the dispersion used to prepare the slurry, the resulting cathode slurry also has a sharp and significant dependence of viscosity on shear rate, as shown in Figure 4 (diamonds, curve 3). The flow behavior index n is 0.1 and the flow consistency index is 13 Pa s 0.1 It is 46.5s -1 The viscosity measured at a shear rate of 100 s was 0.41 Pa s. -1 Extrapolation of the shear rate dependence of gives an estimated viscosity of about 0.21 Pa s. Such a low viscosity provides process capability for application to current collector plates. -1 At shear rates below 100 nm, the viscosity exceeds 13 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.
[0100] The storage stability of the slurries was determined by varying the distribution of the solid particle content along the height of the slurry layer after storage of the slurries in 50 ml cylindrical test tubes with a diameter of 30 mm. For this purpose, the slurries were placed in test tubes, closed with lids and kept under standard conditions (atmospheric pressure, 25 ° C) for 7 days. The top, middle and bottom thirds of the test tubes were then sampled with a pipette and the weight fractions of the solvent and solid non-volatile components in the samples were determined by drying. For the cathode slurry of this example, the solvent content in the initial slurry was 25.2 wt.%, and after one week of storage, the solvent content was 25.7 wt.% in the top third, 25.0 wt.% in the middle and 24.8 wt.% in the bottom. The difference from the initial solvent content did not exceed 2 relative %, which is significantly smaller than the slurry described in Comparative Example 8 below, indicating the high stability of the resulting slurry.
[0101] The lithium-ion battery cathode was prepared by applying the resulting slurry to a current collector (step 3), drying the applied slurry until a cathode was formed (step 4), and applying a 3.8 g / cm 2 The cathode properties were determined by assembling a cell with a Li anode and Li reference electrode and an electrolyte of 1 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with additional 5% v / v vinyl carbonate. The initial specific capacity of the cathode at a discharge current of 0.02 A / g of the cathode material is 197 mA·h / g of the cathode material.
[0102] A lithium-ion battery was assembled from the obtained cathode and anode with graphite as the active material. A polypropylene separator with a thickness of 25 μm was used. A 0.8 M solution of LiPF6 in a 1:1:1 mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with the addition of 1% v / v vinyl carbonate was used as the electrolyte. The initial battery capacity at a discharge rate of 0.1 C was 1650 mA·h. The dependence of the capacity (referred to as initial capacity) on the number of charge-discharge cycles (charge current 1650 mA, discharge current 1650 mA) is shown in the set of points 3 in Figure 7. The battery capacity exceeds 85% of the initial capacity after 500 cycles.
[0103] Example 4 The dispersion is ML (1+4) It contains 0.3 wt. % of hydrogenated nitrile butadiene rubber Therban® 3406 having a viscosity of 63 Mooney units at 100 °C, a content of nitrile units of 34 wt. %, a residual content of polybutadiene units of less than 0.9 wt. %, a content of units obtained by hydrogenation of conjugated diene units of 65 wt. %, and contains 0.9 wt. % of single-walled carbon nanotubes and their aggregates in dimethyl sulfoxide (DMSO). As in Example 1, a dispersion was prepared using chlorine-modified Tuball® SWCNTs. The diameters of the SWCNTs were distributed in the range of 1.2-2.1 nm, the average diameter was 1.54 nm, the G / D line intensity ratio was 81, and the specific surface area determined from the nitrogen adsorption isotherm was 1220 m 2 / g, and the content of chlorine in the tube SWCNT is 0.24 wt%. Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) shows that the SWCNT contains 0.46 wt% Fe (group 8 metal) impurity. See Figure 1 for a transmission electron micrograph of the SWCNT used. The weight ratio of SWCNT to HNBR in the slurry is 3.
[0104] The dispersion was prepared by mixing the required proportions of DMSO, HNBR and SWCNTs, dispersing in a rotary pulsating apparatus (RPA) with a power consumption of 32 kW, a rotor diameter of 190 mm, a gap between the rotor and stator of 700 μm and a rotor speed of 2940 rpm, sonicating in a 100 liter tank at a frequency of 40 kHz and an acoustic input power of 1600 W sonotrode, and stirring in a 220 liter tank at 30 rpm and approximately 2 s by an anchor stirrer. -1 The dispersion was prepared by repeating 15 alternating stages of slow stirring and settling at a shear rate of 1000 kg / h. The rate of dispersion circulation between the RPA, ultrasonic disperser, and tank was 1000 kg / h; about 32 W·h / kg of energy was applied to the dispersion in the RPA in the dispersion stage (D); about 1.8 W·h / kg was applied to the dispersion in the ultrasonic treatment stage (D); about 2 s -1 The average tank residence time of the dispersion at a shear rate of about 13 minutes in stage (R).
[0105] The single-walled carbon nanotubes are aggregated into bundles. The size distribution (carbon nanotubes and their aggregates) was determined by dynamic light scattering (DLS) of the diluted dispersion to a SWCNT concentration of 0.001 wt% of the dispersion. The volume fraction distribution of the nanotube bundles is bimodal, with hydrodynamic diameters ranging from 300 to 1100 nm and 4 to 8 μm. The first and most intense maximum is at D hm = 520 nm, and the second mode D hm2 is approximately 5.5 μm.
[0106] The dispersion viscosity was measured at a constant temperature of 25°C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The dependence of the viscosity on the shear rate was 0.093 s -1 ~186s -1 The flow behavior index n is 0.16 and the flow consistency index is 21 Pa s 0.16 1 / 6.3s -1 The dispersion viscosity at low shear rates is greater than 98 Pa s and is less than 18.6 s.-1 In the shear rate region above 1.8 Pa s, the shear rate is less than 1.8 Pa s.
[0107] Complex modulus measurements performed with an Anton Paar MCR302 rheometer on a cone-and-plate cell with a cone angle of 1° and an oscillation frequency of 1 Hz showed that for oscillation amplitudes ranging from 0.05° to 0.1°, corresponding to shear strains of 5–10%, the loss modulus G” was between 74 and 102 Pa, implying a high viscosity of the dispersion at relative rest, and the phase angle was between 41° and 50°, characterizing the dispersion as a viscoelastic nonideal fluid.
[0108] The main dispersion parameters are given in the summary table.
[0109] Using the dispersion, 71.4 wt. % of the active material LiNi 0.6 Mn 0.2 Co 0.2 A cathode slurry was prepared containing O2 (NMС622), 28.5 wt% DMSO, 0.021 wt% hydrogenated nitrile butadiene rubber Therban® 3406, and 0.064 wt% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: -120g of active material LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMС622) was mixed with 20 g of the dispersion and 60 g of DMSO (additional amount of solvent was introduced in step (1)), stirred for 30 minutes, and further 80 g of the active material LiNi 0.6 Mn 0.2 Co 0.2 Add O2 (NMС622) to the resulting mixture - stage (1); - Stir for 16 hours to produce a homogenous slurry - Step (2).
[0110] The weight ratio of SWNTs to HNBR is 1. Due to the presence of both SWNTs and HNBR, the resulting cathode slurry has a sharp and significant dependence of viscosity on shear rate. The flow behavior index is 0.14 and the flow consistency index is 22 Pa s0.14 It is 46.5s -1 The viscosity measured at a shear rate of 100 s was 0.82 Pa s. -1 Extrapolation of the shear rate dependence of gives an estimated viscosity of about 0.42 Pa s, which provides a process capacity for application to the current collector plate. -1 At shear rates below 100 nm, the viscosity exceeds 22 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.
[0111] The storage stability of the slurries was determined by changing the distribution of the solid particle content along the height of the slurry layer after storage of the slurries in 50 ml cylindrical test tubes with a diameter of 30 mm. For this purpose, the slurries were placed in test tubes, closed with lids and kept under standard conditions (atmospheric pressure, 25 ° C) for 7 days. The top, middle and bottom thirds of the test tubes were then sampled with a pipette and the weight fraction of water and solid non-volatile components in the samples was determined by drying. For the cathode slurry of this example, the DMSO content in the initial slurry was 28.5 wt. %, and after one week of storage the solvent content was 27.8 wt. % in the bottom third, 28.4 wt. % in the middle and 29.3 wt. % in the top. The difference with the initial solvent content did not exceed 3 relative %, which indicates the high stability of the obtained slurries.
[0112] The lithium-ion battery cathode was prepared by applying the resulting slurry to a current collector (step 3), drying the applied slurry until a cathode was formed (step 4), and applying a 3.6 g / cm 2 The cathode properties were determined by assembling a cell with a Li anode and Li reference electrode and an electrolyte of 1 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with additional 5% v / v vinyl carbonate. The initial specific capacity of the cathode at a discharge current of 0.017 A / g of the cathode material is 176 mA·h / g of the cathode material.
[0113] Lithium-ion batteries were assembled from the obtained cathodes and anodes with graphite as active material. A polypropylene separator with a thickness of 25 μm was used. A 0.8 M solution of LiPF6 in a 1:1:1 mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with the addition of 1% v / v vinyl carbonate was used as the electrolyte. The initial battery capacity at a discharge rate of 0.1 C was 1200 mA·h. The dependence of the capacity (referred to as initial capacity) on the number of charge-discharge cycles (charge current 600 mA, discharge current 1200 mA) is shown in Figure 9. The battery capacity exceeds 80% of the initial capacity after 400 cycles.
[0114] Example 5 The dispersion is ML (1+4) It contains 0.4% by weight of partially hydrogenated nitrile butadiene rubber Therban® LT 2057 with a viscosity of 67 Mooney units at 100 ° C, the content of nitrile units is 21% by weight, the residual content of polybutadiene units is 5.5% by weight, the content of units obtained by hydrogenation of conjugated diene units is 73.5% by weight, and contains 0.4% by weight of single-walled carbon nanotubes and their aggregates in dimethylacetamide (DMAA). The dispersion was produced using Tuball™ SWCNTs that were subjected to a multi-stage chemical treatment and boiled in nitric acid for 4 hours. Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-AES) shows that the Fe content in the SWCNTs is 600 ppm or 0.06% by weight. Potentiometric titration shows that the SWCNT surface after such treatment contains about 0.62% by weight of carboxyl groups. The diameter of the SWCNTs ranges from 1.2 to 2.1 nm, with an average diameter of 1.60 nm, a G / D line intensity ratio of 24, and a specific surface area of 1280 m2 determined from the nitrogen adsorption isotherm. 2 The weight ratio of the single-walled carbon nanotubes to the HNBR in the slurry is 1.
[0115] Dispersions were prepared by mixing the required proportions of DMAA, HNBR, and SWCNTs and dispersing six-fold in a NETZSCH Omega 500 high pressure homogenizer at a pressure of 45 MPa and a dispersion transfer rate of 500 kg / h. The estimated shear rate in the nozzle was approximately 10 6 s -1 The power consumption was 5.8 kW, and the specific input energy in stage (D) was about 11.6 W·h / kg. Between each of the two dispersion stages, the dispersion was placed in a 65 L tank and stirred for about 3 s by a gate agitator. -1 The mixture was stirred slowly for 7 minutes at a shear rate of 1000 rpm.
[0116] The viscosity was measured at a constant temperature of 25 °C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The dependence of the viscosity on the shear rate was 0.093 s -1 ~186s -1 The flow behavior index n is 0.26 and the flow consistency index is 14.5 Pa s 0.26 1 / 6.3s -1 The dispersion viscosity at low shear rates is greater than 56 Pa s and is less than 18.6 s. -1 In the region of shear rates above 1.7 Pa s, the shear strength is less than 1.7 Pa s.
[0117] The single-walled carbon nanotubes in the dispersion are aggregated into bundles. The number size distribution of the carbon nanotube bundles was determined by dynamic light scattering (DLS) of the dispersion diluted with NMP to a SWCNT concentration of 0.001 wt%. The number hydrodynamic diameter distribution of the particles (nanotubes and their bundles) in the dispersion obtained by DLS method using a Malvern Zetasizer ZS device is shown by the square curve in Figure 2. Figure 2 shows that the size distribution of the volume fraction of the nanotubes and their aggregates is trimodal, with hydrodynamic diameters in the ranges of 100-600 nm, 600-1100 nm, and 5-9 μm. The first and most intense maximum is at D hm= 295 nm, and a mode D of about 900 nm. h2m A second maximum with a θ of 0.01 μm and a third mode D h3m shows large aggregates (bundles) of single-walled carbon nanotubes having lengths of more than 30 μm.
[0118] The availability of SWNT aggregates with sizes above 10 μm is demonstrated by rapid separation of the dispersion into a solvent containing low SWNT content and a high concentration gel of SWNT and HNBR at oscillatory shear strain of 1 Hz frequency in a cone-and-plate rheometer cell with a cone angle of 1° at a relative shear strain amplitude of more than 100%, as shown in Figure 10 (measurement plate on the left and measurement cone on the right).
[0119] The main dispersion parameters are given in the summary table.
[0120] Using the dispersion, 60.8 wt. % of the active material LiNi 0.33 Mn 0.33 Co 0.33 A cathode slurry was prepared containing O2 (NMС11), 38.2 wt% dimethylacetamide (DMAA) solvent, 0.91 wt% polyvinylidene fluoride (PVDF) binder, 0.024 wt% hydrogenated nitrile butadiene rubber Therban® LT 2057, and 0.024 wt% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - adding 272.5 g of a solution containing 7.5 g of polyvinylidene fluoride (PVDF) binder and 265 g of DMAA to 50 g of dispersion and mixing for 30 minutes on an overhead stirrer - a step of adding binder and solvent carried out prior to step (1); -The resulting mixture was mixed with 300 g of active material LiNi 0.33 Mn 0.33 Co 0.33O2 (NMС11) and stirred for 30 minutes. Another 200 g of active material LiNi 0.33 Mn 0.33 Co 0.33 Add O2 (NMС11) to the resulting mixture - stage (1); - Stir for 16 hours to produce a homogenous slurry - Step (2).
[0121] The lithium-ion battery cathode was prepared by applying the resulting slurry to a current collector (step 3), drying the applied slurry until a cathode was formed (step 4), and applying a 3.5 g / cm 2 The cathode properties were determined by assembling a cell with a Li anode and Li reference electrode and an electrolyte of 1 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with additional 5% v / v vinyl carbonate. The initial specific capacity of the cathode at a discharge current of 0.015 A / g of the cathode material is 151 mA·h / g of the cathode material.
[0122] A lithium-ion battery was assembled from the resulting cathode and anode with graphite as the active material. A polypropylene separator with a thickness of 25 μm was used. A 0.8 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents supplemented with 1% v / v vinyl carbonate was used as the electrolyte. The initial battery capacity was 950 mA·h at a discharge rate of 0.1 C. The battery capacity after 500 charge-discharge cycles is more than 85.3% of the initial capacity (charge current 950 mA, discharge current 950 mA).
[0123] Example 6 The dispersion is ML (1+4)It contains 2% by weight of partially hydrogenated nitrile butadiene rubber Therban® LT 2057 having a viscosity of 67 Mooney units at 100 °C, the content of nitrile units is 21% by weight, the residual content of polybutadiene units is 5.5% by weight, the content of units obtained by hydrogenation of conjugated diene units is 73.5% by weight, and it contains 0.2% by weight of single-walled carbon nanotubes and their agglomerates in ethylene carbonate. The single-walled carbon nanotubes used to prepare the dispersion are Tuball® SWCNTs. The diameter of the SWCNTs is distributed in the range of 1.2-2.1 nm, the average diameter is 1.54 nm, the G / D line intensity ratio is 63, and the specific surface area determined from the nitrogen adsorption isotherm is 1240 m 2 / g. The SWCNTs for preparing the dispersion were further modified with chlorine by the method described in Russian Patent No. 2717516. Energy dispersive spectroscopy indicates that the chlorine content in the tubular SWCNTs is 0.15 wt.%. %. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) indicates that the Fe content in the SWCNTs is 0.68 wt.%. The weight ratio of single-walled carbon nanotubes to HNBR in the slurry is 0.1.
[0124] The dispersion was prepared by mixing 4890 g of ethylene carbonate, 100 g of HNBR and 10 g of SWCNT in a thermostated tank at 50 °C and immersing the dispersion for 2 min. The mixture was subjected to 35 ultrasonic dispersion steps (D) using a sonotrode with an ultrasonic frequency of 22 kHz and an acoustic power of 800 W, alternating with 34 rest steps (R) lasting 2 min each, during which the ultrasound was turned off and the dispersion was stirred for 0.5 s by a blade impeller. -1 The specific input energy at each stage (D) was approximately 5.3 W·h / kg.
[0125] Single-walled carbon nanotubes are aggregated into bundles. The number size distribution of the carbon nanotube bundles was determined by dynamic light scattering (DLS) of a dispersion diluted to a SWCNT concentration of 0.001 wt%. The hydrodynamic diameter distribution of the volume fraction of particles (nanotubes and their bundles) in the dispersion was broad, with hydrodynamic diameters ranging from 200 nm to 3 μm, and D hm = 380 nm mode.
[0126] The dispersion viscosity was measured at a constant temperature of 40 + / - 1 °C (above the melting point of ethylene carbonate) using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The dependence of the viscosity on the shear rate was 0.093 s -1 ~100s -1 The flow behavior index n is 0.03 and the flow consistency index is 3.4 Pa s 0.03 1 / 6.3s -1 The dispersion viscosity in the low shear rate region is greater than 20.3 Pa s and is less than 18.6 s. -1 In the region of shear rates above 100, the shear strength is less than 0.2 Pa s.
[0127] The main dispersion parameters are given in the summary table.
[0128] The dispersion was used to prepare 65.93 wt. % active material LiNi 0.33 Mn 0.33 Co 0.33 A cathode slurry was prepared containing O2 (NMС111), 32.6 wt% ethylene carbonate solvent, 0.67 wt% hydrogenated nitrile butadiene rubber Therban® LT 2057, and 0.07 wt% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: -73.35g of dispersion was mixed with 100g of active material LiNi 0.33 Mn 0.33 Co 0.33 O2 (NMС11) at a temperature of 50 °C and stirred for 30 min. Another 48.35 g of active material LiNi 0.33 Mn 0.33 Co0.33 Add O2 (NMС11) to the resulting mixture - stage (1); Stir at a temperature of -50°C for 16 hours to produce a homogenous slurry - step (2).
[0129] The lithium-ion battery cathode was prepared by applying the resulting slurry to a current collector, drying the applied slurry until a cathode was formed, and applying a 3.5 g / cm 2 The cathode properties were determined by assembling a cell with a Li anode and Li reference electrode and an electrolyte of 1 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with additional 5% v / v vinyl carbonate. The initial specific capacity of the cathode at a discharge current of 0.015 A / g of the cathode material is 152 mA·h / g of the cathode material.
[0130] A lithium-ion battery was assembled from the resulting cathode and anode with graphite as the active material. A polypropylene separator with a thickness of 25 μm was used. A 0.8 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents supplemented with 1% v / v vinyl carbonate was used as the electrolyte. The initial battery capacity was 2230 mA·h at a discharge rate of 0.1 C. The battery capacity after 500 charge-discharge cycles is more than 85.8% of the initial capacity (charge current 2230 mA, discharge current 2230 mA).
[0131] Example 7 The dispersion is ML (1+4)The dispersion contains 0.2 wt. % of partially hydrogenated nitrile butadiene rubber Therban® 3496 having a viscosity of 55 Mooney units at 100°C, a content of nitrile units of 34 wt. %, a residual content of polybutadiene units of 18 wt. %, a content of units obtained by hydrogenation of conjugated diene units of 48 wt. %, and 2 wt. % of single-walled carbon nanotubes and their aggregates in a solution containing N-methyl-2-pyrrolidone (NMP) and dimethyl sulfoxide (DMSO) in a 1:1 wt. ratio. The single-walled carbon nanotubes used to prepare the dispersion are Tuball® SWCNTs. The diameters of the SWCNTs are distributed in the range of 1.2-2.1 nm, the average diameter is 1.62 nm, the G / D line intensity ratio is 46, and the specific surface area determined from the nitrogen adsorption isotherm is 580 m 2 / g. Thermogravimetry data in 5% oxygen flow in Ar indicates that the ash content is about 20 wt% after oxidation of the material at 950 °C. The ash contains mainly iron oxide Fe2O3. X-ray diffraction data indicates that the SWCNTs contain nano-dispersed metallic iron phase. Energy dispersive spectroscopy data indicates that the Fe content in the SWCNTs is 14.2 wt%, which is consistent with the ash weight data. The weight ratio of single-walled carbon nanotubes to HNBR in the slurry is 10.
[0132] The required proportions of water, polyvinylpyrrolidone and SWCNTs were mixed and the dispersion was mixed for approximately 2 s between a Chaoli GJB500 high pressure disperser (stage (D)) at a pressure of 30 MPa and a 65 liter tank (stage (R)) where the dispersion was stationary. -1 The dispersion was prepared by circulating the mixture 32 times at a dispersion transfer rate of 200 kg / h while slowly stirring with a gate agitator at a shear rate of 150,000 s. The estimated shear rate in the disperser was 150,000 s. -1 The measured power consumption was 11.4 kW. The specific input energy in the dispersion cycle was about 57 W·h / kg. The average tank residence time in stage (R) was about 20 min.
[0133] The single-walled carbon nanotubes in the dispersion are aggregated into bundles. The size distribution (carbon nanotubes and their aggregates) was determined by dynamic light scattering (DLS) of the dispersion diluted to a SWCNT concentration of 0.001 wt% of the dispersion. The volume fraction distribution of the nanotube bundles is bimodal, with hydrodynamic diameters ranging from 300 to 1100 nm and 5 to 9 μm. The first and most intense maximum is D hm = 560 nm is described by a log-normal hydrodynamic diameter distribution of the volume fraction of the bundle with a mode at .
[0134] The dispersion viscosity was measured at a constant temperature of 25°C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The dependence of the viscosity on the shear rate was 0.093 s -1 ~100s -1 The flow behavior index n is 0.37 and the flow consistency index is 12 Pa s 0.37 1 / 6.3s -1 The dispersion viscosity at low shear rates is greater than 38 Pa s and is less than 18.6 s. -1 In the region of shear rates above 1.9 Pa s, the shear strength is less than 1.9 Pa s.
[0135] Complex modulus measurements performed with an Anton Paar MCR302 rheometer on a cone-and-plate cell with a cone angle of 1° and an oscillation frequency of 1 Hz showed that at oscillation amplitudes ranging from 0.05° to 0.1°, corresponding to shear strains of 5–10%, the loss modulus G” was between 90 and 112 Pa, implying a high viscosity of the dispersion at relative rest, and the phase angle was between 32° and 35°, characterizing the dispersion as a viscoelastic nonideal fluid.
[0136] The main dispersion parameters are given in the summary table.
[0137] Using the dispersion, 57.04 wt% of the active material LiNi 0.33 Mn 0.33 Co 0.33A cathode slurry was prepared containing O2 (NMС11), 41.4 wt% mixture of N-methyl-2-pyrrolidone (NMP) and dimethylsulfoxide (DMSO) solvents in a 1:1 weight ratio, 1.17 wt% polyvinylidene fluoride (PVDF) binder, 0.01 wt% hydrogenated nitrile butadiene rubber Therban® LT 2057, and 0.09 wt% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - adding 702 g of a solution containing 7.5 g of polyvinylidene fluoride (PVDF) binder and 700 g of a mixture of NMP and DMSO solvents in a 1:1 weight ratio (6.82 g) and mixing for 30 minutes on an overhead stirrer - adding additional binder and solvent performed prior to step (1); -The resulting mixture was mixed with 700 g of active material LiNi 0.33 Mn 0.33 Co 0.33 O2 (NMС11) and stirred for 30 minutes. Another 273.5 g of active material LiNi 0.33 Mn 0.33 Co 0.33 Add O2 (NMС11) to the resulting mixture - stage (1); - Stir for 16 hours to produce a homogenous slurry - Step (2).
[0138] The lithium-ion battery cathode was prepared by applying the resulting slurry to a current collector (step 3), drying the applied slurry until a cathode was formed (step 4), and applying a 3.5 g / cm 2 The cathode properties were determined by assembling a cell with a Li anode and Li reference electrode and an electrolyte of 1 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents with additional 5% v / v vinyl carbonate. The initial specific capacity of the cathode at a discharge current of 0.015 A / g of the cathode material is 149 mA·h / g of the cathode material.
[0139] A lithium-ion battery was assembled from the resulting cathode and anode with graphite as the active material. A polypropylene separator with a thickness of 25 μm was used. A 0.8 M solution of LiPF6 in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents supplemented with 1% v / v vinyl carbonate was used as the electrolyte. The initial battery capacity was 3500 mA·h at a discharge rate of 0.1 C. The battery capacity after 700 charge-discharge cycles is more than 82.4% of the initial capacity (charge current 3500 mA, discharge current 3500 mA).
[0140] Example 8 (comparative example). The dispersion contains 1.2 wt. % single-walled carbon nanotubes and their aggregates in N-methyl-2-pyrrolidone (NMP). The dispersion was prepared using the same SWCNT Tuball™ single-walled carbon nanotubes used to prepare the dispersions of Examples 1 and 4: average diameter of 1.54 nm; intensity ratio of G / D lines in the Raman spectrum at a wavelength of 532 nm of 80; specific surface area of 1220 m 2 / g; chlorine content 0.25 wt.%; iron impurity content 0.46 wt.%. The dispersion does not contain HNBR. The dispersion was prepared as in Example 1.
[0141] The dispersion was analyzed by the shear rate (s -1 The viscosity dependence on shear rate is 0.093s -1 ~93s -1 The flow behavior index n is 0.63 and the flow consistency index is 3.0 Pa s 0.63 The flow behavior index is much higher than that of the dispersion containing both SWCNT and HNBR. This is reflected in the flatter viscosity dependence on shear rate. -1 The dispersion viscosity in the low shear rate region is about 13 Pa s, and about 18.6 s. -1The viscosity at high shear rates is approximately 2.2 Pa·s. Thus, the viscosity at high shear rates is significantly higher than that of the dispersion containing both SWCNT and HNBR, and at low shear rates is much lower than that of the dispersion containing both SWCNT and HNBR. Example 9 below demonstrates that the observed differences cannot be explained by a simple additive effect of adding HNBR to the dispersion, but are due to a synergistic effect of having both SWCNT and HNBR on the rheological properties of the dispersion.
[0142] Complex modulus measurements performed with an Anton Paar MCR302 rheometer on a cone-and-plate cell with a cone angle of 1° and an oscillation frequency of 1 Hz showed that for oscillation amplitudes ranging from 0.05° to 0.1°, corresponding to shear strains of 5–10%, the loss modulus G” was between 21 and 26 Pa, implying insufficient viscosity of the dispersion at relative rest, and the phase angle was between 14° and 17°.
[0143] The dispersion was used to prepare a cathode slurry with the same composition and preparation sequence as in Example 1, except that the dispersion contained hydrogenated nitrile butadiene rubber. Due to the higher concentration of SWCNTs in the dispersion, the amount of dispersion added was three times less and a corresponding amount of additional solvent was introduced to maintain the same ratio of SWCNTs to cathode active material.
[0144] The cathode slurry was prepared by a sequence of steps: another 10 g of a solution containing 1 g of polyvinylidene fluoride (PVDF) in 9 g of NMP was added to the 5 g of dispersion and mixed on an overhead stirrer for 30 minutes; the resulting mixture was mixed with 98.83 g of active material LiNiCoAlO2 (NCA) for 30 minutes; 1 g of acetylene black and 15 g of solvent were added to the resulting mixture and stirred for 16 hours to produce a homogenous slurry.
[0145] The viscosity dependence of the resulting anode slurry on shear rate is shown by the dark triangles (curve 8) in Figure 4. This dependence has a flow behavior index n = 0.43 and a flow consistency index of 4.7 Pa s 0.43The viscosity of the slurry is described by the Ostwald-de Waele power law, which is -1 This viscosity is not sufficient to achieve the required technical results that there is no delamination of the cathode slurry during storage and that the cathodes obtained by applying the slurry to a current collector are of high quality, as shown by slurry storage stability studies and cathode application experiments.
[0146] The storage stability of the slurries was determined by changing the distribution of the solid particle content along the height of the slurry layer after storage of the slurries in 50 ml cylindrical test tubes with a diameter of 30 mm. For this purpose, the slurries were placed in test tubes, closed with lids, kept under standard conditions (atmospheric pressure, 25°C) for 7 days, and analyzed similarly to the procedure described in Example 1. A turbid supernatant layer with a thickness of about 4 mm formed on the surface of the slurry in 7 days. For the cathode slurry of this example, the solvent content in the initial slurry was 22.3 wt.%, and after one week of storage, the solvent content was 34.0 wt.% in the upper third, 17.5 wt.% in the middle, and 15.4 wt.% in the lower part. There was significant delamination of the cathode slurry, which prevented application after 7 days.
[0147] If one were to use the resulting cathode slurry to manufacture a cathode, it would not be possible to obtain a high-quality coating of the current collector with the cathode slurry (see FIG. 5 (right photo)). The resulting dispersion without HNBR, and the cathode slurry manufactured with this dispersion, would not be able to obtain the required technical result.
[0148] Example 9 (comparative example). The dispersion contains 1.2% by weight of partially hydrogenated nitrile butadiene rubber Therban® 3496, and in N-methyl-2-pyrrolidone (NMP) has a content of nitrile units of 34% by weight, a residual content of polybutadiene units of 18% by weight and a content of units resulting from hydrogenation of conjugated diene units of 48% by weight. The solution / dispersion was prepared using the same hydrogenated nitrile butadiene rubber as that used to prepare the dispersion of Example 1.
[0149] The dispersion is subjected to shear rate (s -1 ) is characterized by a very weak dependence of viscosity (Pa s) on shear rate. For clarity, the solution viscosity values of the curve are multiplied by a factor of 100. The dependence of viscosity on shear rate is 0.093 s -1 ~100s -1 The flow behavior index n is 0.89 and the flow consistency index is 6.1 mPa s 0.89 The flow behavior index is very high, i.e., the solution behavior is close to that of a Newtonian fluid.
[0150] A comparison of the viscosity dependence on shear rate for the HNBR solution (Comparative Example 9) and the SWCNT dispersion without HNBR (Comparative Example 8) with that of the dispersion containing both SWCNT and HNBR indicates the synergistic effect of the simultaneous presence of SWCNT and HNBR on the dispersion rheology. Table 1. Summary of the compositions and properties of the dispersions of Examples 1 to 9 JPEG2024545798000006.jpg233101 [Industrial Applicability]
[0151] The present invention can be used to produce dispersions of single-walled and / or double-walled carbon nanotubes and their aggregates in liquid phase, cathode slurries, and lithium ion battery cathodes.
Claims
1. A method of manufacturing a rubber composition comprising the steps of: a solvent, most of the molecules of which are electrically neutral; and hydrogenated nitrile butadiene rubber, HNBR. - a dispersion comprising single-walled and / or double-walled carbon nanotubes, the content of said single-walled and / or double-walled carbon nanotubes being in the range of 0.2-2 wt. %, and the weight ratio of said single-walled and / or double-walled carbon nanotubes to said HNBR being at least 0.1 and not more than 10; Dispersion.
2. The dispersion described in claim 1, wherein (i) the HNBR contains more than 15 weight percent hydrogenated polybutadiene units, or (ii) the HNBR contains more than 40 weight percent hydrogenated polybutadiene units and / or less than 1 weight percent residual polybutadiene units.
3. 2. The dispersion of claim 1, wherein the HNBR contains more than 20% by weight of acetonitrile units.
4. 2. The dispersion of claim 1, wherein the solvent is an organic solvent having a flash point of at least 70°C.
5. 5. The dispersion of claim 4, wherein the solvent is an organic solvent which is either N-methyl-2-pyrrolidone, ethylene carbonate, dimethylsulfoxide, dimethylacetamide, or a mixture thereof.
6. 2. The dispersion of claim 1, wherein the single-walled and / or double-walled carbon nanotubes (i) contain at least 0.1 wt. % functional groups on the surface, (ii) contain at least 0.1 wt. % chlorine on the surface, and / or (iii) contain at least 0.1 wt. % carbonyl and / or hydroxyl and / or carboxyl groups on the surface.
7. 2. The dispersion of claim 1, wherein the single-walled and / or double-walled carbon nanotubes are aggregated and the mode of the hydrodynamic diameter distribution of the number of carbon nanotube aggregates is in the range of 100 nm to 1 μm.
8. 8. The dispersion of claim 7, wherein the hydrodynamic diameter distribution of the number of carbon nanotube aggregates has a mode in the range of 300 nm to 800 nm and / or the hydrodynamic diameter distribution of the number of carbon nanotube aggregates has more than one mode.
9. 9. The dispersion of claim 8, wherein the carbon nanotube aggregate number hydrodynamic diameter distribution is characterized by a mode greater than 2 μm.
10. 2. The dispersion of claim 1, wherein upon oscillatory shear strain in a cone and plate rheometer cell having a frequency of 1 Hz and a relative shear strain amplitude of 100%, the dispersion separates into a solvent and a concentrated gel of single-walled and / or double-walled carbon nanotubes and HNBR.
11. 2. The dispersion of claim 1, wherein the dispersion has a ratio of G / D line intensities in a Raman spectrum at a wavelength of 532 nm of at least 10.
12. 2. The dispersion of claim 1, wherein the single-walled and / or double-walled carbon nanotubes and / or aggregates thereof contain metal impurities from Groups 8 to 11.
13. 13. The dispersion of claim 12, wherein the single-walled and / or double-walled carbon nanotubes and / or aggregates thereof contain less than 1 wt. % of Group 8 to Group 11 metal impurities.
14. The dispersion has a flow behavior index "n" of 0.37 or less and a viscosity of at least 3.2 Pa.s n 2. The dispersion of claim 1, which is a pseudoplastic fluid having a flow consistency index "K" of
15. The dependency of viscosity on shear rate follows the Ostwald-de Waele power law, and the flow behavior index n and the flow consistency index K satisfy the condition n<1.25*lg(K / (Pa·s n 2. The dispersion according to claim 1, wherein the flow behavior index n and the flow consistency index K satisfy the condition n<1.24-0.787*lg(K / (Pa·s n ))-0.628; and / or the flow behavior index n and the flow consistency index K satisfy the condition n<1.24-0.787*lg(K / (Pa·s n )).
16. 2. The dispersion of claim 1, having a loss modulus greater than 27 Pa at oscillatory shear strain in a cone and plate rheometer cell having a frequency of 1 Hz and a relative shear strain amplitude in the range of 5 to 10% and a phase angle greater than 18° at oscillatory shear strain in a cone and plate rheometer cell having a frequency of 1 Hz and a relative shear strain amplitude in the range of 5 to 10%.
17. A method for producing a dispersion comprising at least three dispersion steps (D) comprising dispersing single-walled and / or double-walled carbon nanotubes in a solvent and at least two resting steps (R), wherein the resting steps (R) alternate between the dispersion steps (D), and any of the dispersion steps (D) is (i) at least 10,000 s -1 or (ii) ultrasonic treatment of the dispersion at a frequency of at least 20 kHz with a specific input energy of at least 1 W·h / kg, wherein the resting step (R) comprises: -1 and exposing the dispersion to a shear rate of less than 100 nm, wherein the dispersing step (D) and the resting step (R) produce a dispersion in which a majority of the molecules of the solvent are electrically neutral, the dispersion comprising 0.2 to 2 weight percent of the single-walled and / or double-walled carbon nanotubes and hydrogenated nitrile butadiene rubber (HNBR), and a weight ratio of single-walled and / or double-walled carbon nanotubes to HNBR of at least 0.1 and no more than 10.
18. 20. The method of claim 17, comprising a series of at least 10 alternating dispersion steps (D) and at least 9 rest steps (R).
19. The sequence of alternating steps (D) and (R) comprises (a) one or several devices providing a mechanical or ultrasonic treatment step, and (b) a step in which the dispersion is held for 10 s. -1 20. The method of claim 18, wherein the dispersion is carried out by circulating the dispersion between a slowly stirred tank at a shear rate of less than 100 rpm.
20. 20. The method of claim 19, wherein the dispersion circulation factor during manufacturing is at least 10.
21. At least 10,000 s with a specific input energy of at least 10 W h / kg -1 and a sonotrode immersed in the dispersion with a specific input energy of at least 1 W h / kg at a frequency of at least 20 kHz, and a shear rate of at least 10 s. -1 The process according to claim 19, wherein the circulation rate between the tank and the slowly stirred tank at a shear rate of less than 100 to 10,000 kg / h.
22. At least 10,000s -1 and a specific input energy of at least 10 W·h / kg; and the dispersion is held for at least 1 minute and then heated to 10 s. -1 The process according to claim 19, wherein the circulation rate between the tank and the slowly stirred tank at a shear rate of less than 100 to 10,000 kg / h.
23. 1. A method for producing a cathode slurry, the method comprising: (1) mixing a lithium-containing active material with a dispersion; and (2) agitating the resulting mixture to produce a homogenous slurry, the dispersion comprising: (i) a solvent, wherein most of the molecules of the solvent are electrically neutral; (ii) hydrogenated nitrile butadiene rubber, HNBR; and (iii) single-walled and / or double-walled carbon nanotubes, the content of the single-walled and / or double-walled carbon nanotubes being in the range of 0.2-2 wt. %, and the weight ratio of the single-walled and / or double-walled carbon nanotubes to the HNBR being at least 0.1 and no more than 10.
24. 24. The method of claim 23, wherein a solvent and / or one or several binders and / or conductive additives are also added to the mixture in the mixing step (1).
25. The method of claim 23, further comprising one or more additional steps of mixing one or more binders and / or conductive additives into the solvent, in addition to stirring the resulting mixture to produce a homogenous slurry.